Cerium oxide particles, slurry composition for chemical mechanical polishing containing the same, and method for manufacturing semiconductor device
Cerium oxide particles with controlled size and Ce 3+ content in a transparent CMP slurry composition address the challenge of high oxide film removal rates and reduced polishing scratches, enhancing semiconductor device miniaturization and efficiency.
Patent Information
- Application Number
- JP2023513884
- Authority / Receiving Office
- JP · JP
- Patent Type
- Patents
- Current Assignee / Owner
- Priority Date
- 2021-07-02
- Filing Date
- 2021-08-30
- Publication Date
- 2025-01-14
- Estimated Expiration
- 2041-08-30
AI Technical Summary
Conventional cerium oxide slurries used in chemical mechanical polishing (CMP) face challenges in achieving high oxide film removal rates while maintaining small particle sizes, leading to issues with polishing scratches and reduced mechanical action, which hinder the advancement of semiconductor device miniaturization.
The development of cerium oxide particles with a specific composition and size distribution, characterized by a high ratio of Ce 3+ on the surface, monodispersity, and controlled particle sizes ranging from 1 to 30 nm, which are incorporated into a transparent CMP slurry composition, enhancing polishing efficiency and reducing surface defects.
The cerium oxide particles maintain a high oxide film removal rate with minimal surface defects, allowing for improved polishing performance and increased miniaturization capabilities in semiconductor manufacturing.
Smart Images

Figure 0007612839000024 
Figure 0007612839000025 
Figure 0007612839000026
Abstract
Description
[Technical field]
[0001] The present invention relates to cerium oxide particles for chemical mechanical polishing, a slurry composition for chemical mechanical polishing containing the same, and a method for manufacturing a semiconductor device. More specifically, unlike existing cerium oxide particles, the present invention relates to a method for forming Ce on the surface of cerium oxide through synthesis. 3+ The present invention relates to a slurry composition for chemical mechanical polishing having a high oxide film removal rate at a low content despite its small particle size by increasing the ratio of [Background technology]
[0002] As semiconductor devices become more diverse and highly integrated, finer pattern forming techniques are being used, which makes the surface structure of the semiconductor device more complicated, and the interlayer flatness in each process is a very important factor for improving the accuracy of photolithography. In manufacturing semiconductor devices, a chemical mechanical polishing (CMP) process is used as such a planarization technique. For example, it is widely used as a process for removing an excessively formed insulating film for interlayer insulation, a process for planarizing an insulating film for shallow trench isolation (STI) that insulates between an interlayer insulating film (ID) and a chip, and a process for forming metal conductive films such as wiring, contact plugs, and via contacts.
[0003] In the CMP process, the polishing speed, the flatness of the polished surface, and the degree of scratch generation are important, and are determined by the conditions of the CMP process, the type of slurry, the type of polishing pad, etc. High-purity cerium oxide particles are used in the cerium oxide slurry. In recent years, in the manufacturing process of semiconductor devices, there is a demand to achieve even finer wiring, and polishing scratches that occur during polishing have become a problem.
[0004] Conventional cerium oxide slurries use particles with sizes between 30nm and 200nm, and even if fine polishing scratches occur during polishing, they are not a problem as long as they are smaller than the conventional wiring width, but this is currently a problem in the ongoing pursuit of finer wiring. In response to this problem, attempts have been made to reduce the average particle size of the cerium oxide particles, but with existing particles, reducing the average particle size reduces the mechanical action, resulting in a problem of a slower polishing speed.
[0005] Thus, even if one attempts to control the polishing rate and polishing scratches by controlling the average particle size of the cerium oxide particles, it is extremely difficult to achieve a target level of polishing scratches while maintaining the polishing rate.
[0006] In addition, in the conventional slurry composition for chemical mechanical polishing, the cerium oxide particles are 3+ vs Ce 4+ The ratio of Ce on the cerium oxide surface is optimized, and at the same time, the average particle size is not optimized. 3+ In reality, research is needed on polishing slurries containing cerium oxide particles that exhibit a high oxide film removal rate despite their small particle size by increasing the ratio of cerium oxide particles. Summary of the Invention [Problem to be solved by the invention]
[0007] The present invention has been devised to solve the above problems, and one embodiment of the present invention provides cerium oxide particles for chemical mechanical polishing.
[0008] Another embodiment of the present invention provides a slurry composition for chemical mechanical polishing.
[0009] Further, another embodiment of the present invention provides a method for manufacturing a semiconductor device, comprising the step of polishing using the above-mentioned slurry composition for chemical mechanical polishing.
[0010] Yet another embodiment of the present invention provides a semiconductor device.
[0011] Yet another embodiment of the present invention provides a method for producing cerium oxide particles for chemical mechanical polishing.
[0012] However, the technical problems that the present invention aims to achieve are not limited to those mentioned above, and other technical problems not mentioned will be clearly understood by a person having ordinary skill in the art to which the present invention pertains from the following description. [Means for solving the problem]
[0013] As a technical means for achieving the above-mentioned technical object, one aspect of the present invention provides cerium oxide particles for chemical mechanical polishing, characterized in that in an aqueous dispersion in which the content of the cerium oxide particles is adjusted to 1.0 wt %, the light transmittance for light with a wavelength of 500 nm is 50% or more.
[0014] The present invention may be characterized in that an average light transmittance for light having a wavelength of 450 to 800 nm is 50% or more in an aqueous dispersion in which the content of the cerium oxide particles is adjusted to 1.0% by weight.
[0015] When the cerium oxide particles are contained in a chemical mechanical polishing slurry, the chemical mechanical polishing slurry may be characterized as being transparent.
[0016] The cerium oxide particles may be characterized as being monodispersed when contained in a slurry for chemical mechanical polishing.
[0017] The secondary particle diameter of the cerium oxide particles, as measured by a dynamic light scattering (DLS) particle size analyzer, may be 1 to 30 nm.
[0018] The secondary particle diameter of the cerium oxide particles, as measured by a dynamic light scattering (DLS) particle size analyzer, may be 1 to 20 nm.
[0019] When analyzed by X-ray diffraction (XRD), the cerium oxide particles may be characterized in that the primary particle size is 0.5 to 15 nm.
[0020] When analyzed by transmission electron microscopy (TEM), the cerium oxide particles may be characterized as having a particle size of 10 nm or less.
[0021] When analyzed by small angle X-ray scattering (SAXS), the cerium oxide particles may be characterized by a particle size of 0.5 to 15 nm.
[0022] In the spectrum measured by Fourier transform infrared (FT-IR) spectroscopy, -1 ~3600cm -1 Infrared transmittance is over 90% in the range of 720 cm -1 ~770cm -1 In the above range, the infrared transmittance may be 96% or less.
[0023] On the surface of the cerium oxide particles, X-ray photoelectron spectroscopy (XPS) analysis revealed that Ce 3+ The XPS peaks indicating the Ce—O bond energy may be characterized as appearing at a first peak of 900.2 to 902.2 eV, a second peak of 896.4 to 898.4 eV, a third peak of 885.3 to 887.3 eV, and a fourth peak of 880.1 to 882.1 eV.
[0024] In the X-ray photoelectron spectroscopy (XPS) analysis, the ratio of Ce to the sum of the XPS peak areas showing the Ce-O bond energy on the surface of the cerium oxide particles was 3+ The ratio of the sum of the XPS peak areas showing the Ce—O bond energy may be 0.29 to 0.70.
[0025] 455cm -1~460cm -1 The Raman peak may be characterized as having a first Raman peak in the band range of
[0026] 586cm -1 ~627cm -1 The compound may further be characterized by having a second Raman peak in the band range of
[0027] 712cm -1 ~772cm -1 The compound may further be characterized by having a third Raman peak in the band range of
[0028] The ratio (A / B) of the first Raman peak intensity (A) to the second Raman peak intensity (B) may be 25 or less.
[0029] The ratio (A / C) of the first Raman peak intensity (A) to the third Raman peak intensity (C) may be 50 or less.
[0030] The electron energy loss spectroscopy (EELS) spectrum may be characterized as including a first peak between 876.5 and 886.5 eV and a second peak between 894.5 and 904.5 eV, with the maximum intensity of the first peak being greater than the maximum intensity of the second peak.
[0031] The sum of the total areas of the peaks in the spectrum (P t The ratio of the sum of the areas of the third peak section (P1) and the sum of the areas of the fourth peak section (P2) to the sum of the areas of the third peak section (P1) and the fourth peak section (P2) ((P1+P2) / P t ) may be less than or equal to 0.1.
[0032] Ce by X-ray absorption fine structure (XAFS) spectroscopy 3+ The areas of the peaks A3 and Ce 4+Ce relative to the sum of the areas A4 of the peaks 3+ The ratio (A3 / (A3+A4)) of the area A3 of the peak showing the above may be 0.03 or more.
[0033] Ce by XAFS (X-ray absorption fine structure) spectroscopy 3+ The areas of the peaks A3 and Ce 4+ For the sum of the areas A4 of the peaks showing Ce 3+ The ratio A3 / (A3+A4) of the areas A3 of the peaks showing the above can be 0.1 or more.
[0034] When measuring the XAFS spectrum, the maximum optical absorption coefficient of the first peak may be in the range of 5730 eV or more and less than 5740 eV, and the maximum optical absorption coefficient of the first peak may be 0.1 to 0.4.
[0035] When measuring the XAFS spectrum, the maximum optical absorption coefficient of the second peak may be in the range of 5740 eV to 5760 eV, and the maximum optical absorption coefficient of the second peak may be less than 0.6.
[0036] The cerium oxide particles may be characterized in that the maximum number of photoelectrons emitted per second in an ultraviolet photoelectron spectroscopy (UPS) analysis is in a range of kinetic energy of 10 eV or less.
[0037] The cerium oxide particles may be characterized in that the maximum number of photoelectrons (Counts) emitted per second during UPS analysis is in the range of kinetic energy of 3 to 10 eV.
[0038] The cerium oxide particles may be characterized by having a work function value of 3.0 eV to 10.0 eV when analyzed by UPS.
[0039] The cerium oxide particles have a BET surface area of 50 m 2 / g or less.
[0040] The cerium oxide particles may be characterized in that the apparent density measured by a static method is 2.00 to 5.00 g / ml.
[0041] The cerium oxide particles may be characterized in that the apparent density measured by a tapping method is 2.90 to 5.00 g / ml.
[0042] When photoluminescence (PL) intensity is measured at a wavelength of 325 nm for an aqueous dispersion in which the content of the cerium oxide particles is adjusted to 1.0 wt %, the maximum intensity of the first peak (λ1) at a wavelength of 435 to 465 nm appears in the range of 0.1 to 30.
[0043] It may be characterized in that the maximum intensity of the second peak (λ2) at a wavelength of 510 to 540 nm appears in the range of 0.1 to 10.
[0044] The intensity ratio (λ1 / λ2) of the first peak (λ1) to the second peak (λ2) having a wavelength of 510 to 540 nm may be 5 to 15.
[0045] When the color of the aqueous dispersion in which the content of the cerium oxide particles is adjusted to 1.0 wt % is expressed in the L*a*b* color system, the L* value may be 95 or more and the b* value may be 10 to 25.
[0046] (L* indicates lightness, a* indicates redness, and b* indicates yellowness)
[0047] The a* may be in the range of -12 to -3.
[0048] The cerium oxide particles may have a sedimentation rate of 25% by weight or less when an aqueous dispersion containing 1.0% by weight of the cerium oxide particles is centrifuged at a centrifugal force of 4250 G for 30 minutes.
[0049] Another aspect of the present invention provides a slurry composition for chemical mechanical polishing, comprising cerium oxide particles and a solvent, and characterized in that in an aqueous dispersion in which the content of the cerium oxide particles is adjusted to 1.0 wt %, the composition has a light transmittance of 50% or more for light with a wavelength of 500 nm.
[0050] The cerium oxide particles may be included in an amount of 0.01 to 5 parts by weight based on 100 parts by weight of the total slurry composition.
[0051] The composition may be characterized in that the pH is 2-10.
[0052] The chemical mechanical polishing slurry composition may be characterized by one or more inorganic acids selected from the group consisting of sulfuric acid, hydrochloric acid, nitric acid, and phosphoric acid; one or more organic acids selected from the group consisting of acetic acid, citric acid, glutaric acid, glycolic acid, formic acid, lactic acid, malic acid, malonic acid, maleic acid, oxalic acid, phthalic acid, succinic acid, and tartaric acid; one or more amino acids selected from the group consisting of lysine, glycine, alanine, arginine, valine, leucine, isoleucine, methionine, cysteine, proline, histidine, phenylalanine, serine, tricine, tyrosine, aspartic acid, tryptophan, and aminobutyric acid; imidazole; alkylamines; alcohol amines; quaternary amine hydroxides; ammonia; or combinations thereof.
[0053] The solvent may be deionized water.
[0054] The chemical mechanical polishing slurry composition may be characterized by having a polishing rate for a silicon oxide film of 1,000 to 5,000 Å / min.
[0055] Another aspect of the present invention provides a slurry composition for chemical mechanical polishing, comprising: cerium oxide particles; and a solvent; wherein the cerium oxide particles are produced by a wet method, and the content of a precursor material contained in the slurry composition is 300 ppm or less by weight.
[0056] The slurry composition for chemical mechanical polishing contains 0.001 to 5% or less of the cerium oxide particles based on the total weight of the composition.
[0057] Another aspect of the present invention provides a slurry composition for chemical mechanical polishing, comprising: cerium oxide particles; a solvent; and a cationic polymer.
[0058] The oxide film polishing rate may be increased depending on the content of the cationic polymer.
[0059] The cationic polymer may be characterized by increasing the polishing selectivity of an oxide film / a polysilicon film.
[0060] The content of the cationic polymer may be 0.001 to 1 wt % based on the total weight of the slurry composition for chemical mechanical polishing.
[0061] The cationic polymer may be characterized as a polymer or copolymer containing an amine group or an ammonium group.
[0062] The cationic polymer may be polydiallyldimethyl ammonium chloride, polyallylamine, polyethyleneimine, polydiallylamine, polypropyleneimine, polyacrylamide-co-diallydimethyl ammonium chloride, polyacrylamide, poly(trimethylammonio ethyl methacrylate), dicyandiamide-diethylenetriamine copolymer, diallyldimethylamine / hydrochloride-acrylamide copolymer, dicyandiamide-formaldehyde copolymer, or a combination thereof.
[0063] The chemical mechanical polishing slurry composition may be characterized by having an oxide film / polysilicon film polishing selectivity of 200-2,000.
[0064] In another aspect of the present invention, there is provided a method for manufacturing a semiconductor device, comprising the step of polishing using the above-mentioned slurry composition for chemical mechanical polishing.
[0065] Another aspect of the present invention provides a semiconductor device comprising: a substrate; and a trench on the substrate, the trench being filled with an insulating material, the trench being produced by polishing at least one film selected from the group consisting of a silicon oxide film, a silicon nitride film, and a polysilicon film, using a slurry composition for chemical mechanical polishing, the slurry composition for chemical mechanical polishing comprising cerium oxide particles and a solvent, the slurry composition having an optical transmittance of 50% or more for light having a wavelength of 500 nm in an aqueous dispersion in which the content of the cerium oxide particles is adjusted to 1.0% by weight.
[0066] Another aspect of the present invention is a method for producing a fluororesin comprising the steps of: preparing a raw material precursor; and pulverizing or precipitating cerium oxide particles in a solution containing the raw material precursor to obtain a dispersion of cerium oxide particles for chemical mechanical polishing;
[0067] The present invention provides a method for producing cerium oxide particles for chemical mechanical polishing, characterized in that in an aqueous dispersion in which the content of the cerium oxide particles is adjusted to 1.0% by weight, the optical transmittance for light with a wavelength of 500 nm is 50% or more. Effect of the Invention
[0068] In the case of the cerium oxide particles according to one embodiment of the present invention, the Ce on the surface of the cerium oxide 3+ By increasing the ratio of, when it is contained in a slurry for chemical mechanical polishing, it is possible to maintain a high oxide film removal rate even at a low content, despite the small particle size.
[0069] In addition, according to one embodiment of the present invention, it is possible to provide cerium oxide particles for a slurry composition for chemical mechanical polishing, which can minimize surface defects on a wafer and maximize the oxide film removal rate, unlike the correlation between surface defects and oxide film removal rate, which has previously been considered to be in a trade-off relationship, and which can minimize surface defects while maximizing the oxide film removal rate.
[0070] In addition, according to one embodiment of the present invention, it is confirmed that the addition of a cationic polymer further increases the oxide film polishing rate and at the same time increases the oxide film / polysilicon film selectivity. Considering the conventional technical common sense that the addition of a cationic polymer usually sacrifices the polishing rate to secure other properties, this can be said to be a unique effect of the present invention.
[0071] The effects of the present invention are not limited to the effects described above, but should be understood to include all effects that can be inferred from the configuration of the invention described in the detailed description of the present invention or the claims. [Brief description of the drawings]
[0072] [Figure 1] 1 shows an oxide film removal mechanism according to an embodiment of the present invention. [Diagram 2] 1 is a cross-sectional view (1) showing a method for manufacturing a semiconductor device according to an embodiment of the present application. [Diagram 3] 2 is a cross-sectional view (2) illustrating a method for manufacturing a semiconductor device according to an embodiment of the present disclosure. [Figure 4] 3 is a cross-sectional view (3) illustrating a method for manufacturing a semiconductor device according to an embodiment of the present disclosure. [Diagram 5] 4 is a cross-sectional view (4) illustrating a method for manufacturing a semiconductor device according to an embodiment of the present disclosure. [Figure 6] 1A to 1C are cross-sectional views illustrating a method of manufacturing a semiconductor device according to an embodiment of the present disclosure. [Figure 7] 1 shows a step-by-step process of chemical mechanical polishing and the structure of a chemical mechanical polishing (CMP) equipment according to another embodiment of the present application (1). [Figure 8] 2 shows a stepwise process of chemical mechanical polishing and the structure of a chemical mechanical polishing (CMP) equipment according to another embodiment of the present application (2). [Figure 9] This is an image obtained by visually observing a dispersion liquid in which conventional cerium oxide particles are dispersed. [Figure 10] 1 is a visual image of a dispersion liquid in which cerium oxide particles according to an embodiment of the present invention are dispersed. [Figure 11] 1 is a TEM image (1) of cerium oxide particles according to one embodiment of the present invention. [Figure 12] 2 is a TEM image (2) of cerium oxide particles according to one embodiment of the present invention. [Figure 13] 3 is a TEM image of cerium oxide particles according to an embodiment of the present invention (3). [Figure 14] 2 is a SEM image of cerium oxide particles according to Comparative Example 1. [Figure 15] 1 is a SEM image of cerium oxide particles according to Comparative Example 2. [Figure 16] 4 shows SEM and TEM images of cerium oxide particles according to Comparative Example 3. [Figure 17] 1 is a SEM image of cerium oxide particles according to Comparative Example 4. [Figure 18] TEM images of Comparative Examples 1 to 3. [Figure 19] 2 is a particle size analysis result of the cerium oxide particles according to an embodiment of the present invention by X-ray diffraction (XRD). [Figure 20] 1 is a result of analysis of cerium oxide particles according to an embodiment of the present invention by small angle X-ray scattering (SAXS). [Figure 21] 2 is a result of dynamic light scattering (DLS) particle size analysis of cerium oxide particles according to an embodiment of the present invention. [Figure 22] 1 shows the results of spectrum analysis of cerium oxide particles and cerium hydroxide particles according to an embodiment of the present invention by Fourier transform infrared (FT-IR) spectroscopy. [Figure 23] 1 shows the results of measuring the light transmittance of slurries containing cerium oxide particles according to an example of the present invention and conventional cerium oxide particles of Comparative Examples 1 to 4 using ultraviolet-visible (UV-vis) spectroscopy. [Figure 24] 2 shows the intensity ratio and peak area results of XRD (X-ray diffraction) analysis of the cerium oxide particles according to an embodiment of the present invention. [Diagram 25]2 is a result of an X-ray photoelectron spectroscopy (XPS) analysis of the cerium oxide particles according to an embodiment of the present invention. [Figure 26] 1 shows the results of X-ray photoelectron spectroscopy (XPS) analysis of cerium oxide particles according to Comparative Example 3. [Figure 27] 1 is a Raman peak analysis result of cerium oxide particles according to an embodiment of the present invention. [Figure 28] 3 shows the results of Raman peak analysis of the cerium oxide particles according to Comparative Example 1. [Figure 29] 1 shows the results of Raman peak analysis of cerium oxide particles according to Comparative Example 3. [Diagram 30] 2 is an electron energy loss spectroscopy (EELS) analysis result of the cerium oxide particles according to an embodiment of the present invention. [Diagram 31] 1 shows the results of electron energy loss spectroscopy (EELS) analysis of cerium oxide particles according to Comparative Example 3. [Diagram 32] 1 shows the results of electron energy loss spectroscopy (EELS) analysis of the cerium oxide particles according to Comparative Example 4. [Diagram 33] 1 is a result of an X-ray absorption fine structure (XAFS) spectrum analysis of a cerium oxide particle according to an embodiment of the present invention. [Diagram 34] 1 shows the results of X-ray absorption fine structure (XAFS) spectrum analysis of the cerium oxide particles according to Comparative Example 3. [Diagram 35] 1 shows the results of ultraviolet photoelectron spectroscopy (UPS) analysis of an aqueous dispersion containing 1 mass % of cerium oxide particles according to an embodiment of the present invention. [Diagram 36] 1 shows the results of ultraviolet photoelectron spectroscopy (UPS) analysis of an aqueous dispersion containing 1 mass % of cerium oxide particles according to Comparative Example 3. [Figure 37] 1 shows the results of ultraviolet photoelectron spectroscopy (UPS) analysis of an aqueous dispersion containing 1 mass % of cerium oxide particles according to Comparative Example 4. [Figure 38] 1 is a BET surface area measurement result of cerium oxide particles according to an embodiment of the present invention. [Figure 39] 2 shows the results of BET surface area measurement of cerium oxide particles according to Comparative Example 1. [Diagram 40] 1 shows the results of measuring the photoluminescence (PL) intensity of cerium oxide particles according to an embodiment of the present invention. [Diagram 41] 1 shows the results of measuring the luminescence intensity (PL) of cerium oxide particles according to Comparative Example 3. [Diagram 42] 1 shows the results of measuring the luminescence intensity (PL) of cerium oxide particles according to Comparative Example 4. [Diagram 43] 1 is a dispersion containing 1 mass % of cerium oxide particles according to an embodiment of the present invention, prepared for measuring a color system. [Diagram 44] This is a dispersion containing 1 mass % of cerium oxide particles according to Comparative Example 3, prepared for measuring the color system. [Diagram 45] 1 shows scanned images (1) of an oxide wafer before and after CMP using a CMP slurry composition containing cerium oxide particles according to an embodiment of the present invention and a CMP slurry composition containing cerium oxide particles of 60 nm class. [Diagram 46] 1 is a scanned image (2) of an oxide wafer before and after CMP using a CMP slurry composition containing cerium oxide particles according to an embodiment of the present invention and a CMP slurry composition containing cerium oxide particles of 60 nm class. [Figure 47] 4 shows the results of measuring the behavior of oxide film polishing rate depending on the addition of a cationic polymer to a CMP slurry composition including cerium oxide particles according to an embodiment of the present invention. DETAILED DESCRIPTION OF THE PREFERRED EMBODIMENTS
[0073] DETAILED DESCRIPTION OF THE PREFERRED EMBODIMENTS The present invention will now be described in detail with reference to exemplary embodiments thereof so that those skilled in the art can easily practice the present invention. However, the present invention may be embodied in many different forms and should not be construed as limited to the exemplary embodiments set forth herein.
[0074] Production Example 1. Production of cerium oxide particles The cerium oxide particles according to an embodiment of the present invention may be synthesized through a bottom-up chemical synthesis. In the present embodiment, the cerium oxide particles were synthesized by any one of the following methods for producing cerium oxide particles.
[0075] According to a manufacturing method according to an embodiment of the present application, first, about 2 to 4 kg of cerium nitrate was added to a sufficient amount of deionized water and stirred. Nitric acid was added to the precursor solution to adjust the pH to 1.0 or less. Ammonia water was added and stirred until a precipitate was formed in the manufactured mixture. It was confirmed that the pH of the stirred mixture was strongly acidic (2 or less), and that if the mixture was left to stand after the stirring was completed, the product would precipitate quickly. After removing the supernatant liquid (supernatant) from which the precipitate was removed, a certain amount of deionized water was added, and a light yellow cerium oxide particle dispersion was produced. The manufactured dispersion was circulated and filtered through a membrane filter to obtain a transparent yellow cerium oxide dispersion.
[0076] According to another embodiment of the present invention, 150 g of cerium oxide or cerium hydroxide was dispersed in 3 kg of deionized water and stirred to a degree that particles did not precipitate. Nitric acid was added to the mixture until the pH was 1.0 or less. The mixture was added to a milling machine filled with 0.05 mm zirconia beads and pulverized while circulating at 4,000 rpm. As the milling proceeded, it was observed that the opaque white cerium oxide dispersion gradually changed to a transparent yellow cerium oxide dispersion. The transparent yellow cerium oxide dispersion produced after the milling was circulated and filtered through a membrane filter to obtain a pure transparent yellow cerium oxide dispersion.
[0077] According to a manufacturing method according to another embodiment of the present application, first, about 2 to 4 kg of ceric ammonium nitrate was added to a sufficient amount of ethanol and stirred. An imidazole solution was added to the precursor solution and stirred until a precipitate was formed. It was confirmed that the pH of the stirred mixture was strongly acidic (2 or less), and that if the mixture was left to stand after stirring was completed, the product would precipitate quickly. After removing the supernatant liquid from which the precipitate had been removed, a certain amount of deionized water was added to produce a cerium oxide particle dispersion. The produced dispersion was circulated and filtered using a membrane filter to obtain a transparent cerium oxide dispersion.
[0078] According to another embodiment of the present invention, 1.1 kg of cerium nitrate and 10 kg of deionized water were mixed in a reaction vessel. The stirring speed of the reaction vessel was maintained at 200 rpm, and the temperature was maintained at room temperature. A 1:1 mixture of 25% ammonia solution and deionized water was prepared and added to the reaction vessel until the pH reached 7.0. After stirring for 1 hour, a 1:1 mixture of 70% nitric acid and deionized water was added until the pH reached 1.0. The temperature of the reaction vessel was raised to 100°C, and the reaction was carried out for 4 hours. During the reaction, the light purple giant particles were dissociated, and yellow transparent cerium oxide nanoparticles were produced. The obtained particles were circulated through a membrane filter to remove the pure water, and a pure cerium oxide nanoparticle dispersion was obtained.
[0079] Production Example 2. Production of CMP slurry containing cerium oxide particles The cerium oxide particles prepared in Preparation Example 1 were added to deionized water to adjust the abrasive concentration to 0.05 wt %, and triethanolamine was added to adjust the pH to 5.5 to prepare a CMP slurry.
[0080] 9 and 10, it can be seen that the slurry containing conventional ceria particles has a high turbidity even when observed with the naked eye, whereas the slurry containing the cerium oxide particles of the present invention can be observed to be transparent, and it can be inferred that the slurry has monodisperse properties.
[0081] Comparative Examples 1 to 4. Preparation of conventional slurry compositions containing ceria particles Commercially available wet cerium oxide particles with average particle sizes of 10, 30, and 60 nm, and cerium oxide particles of 10 to 20 nm class separately produced by a calcination method were obtained and added to deionized water to adjust the abrasive concentration to 0.05 wt %, and ammonia was added as a pH adjuster to a final pH of 5.5 to produce CMP slurries.
[0082] Experimental Example 1. SEM and TEM analysis of cerium oxide particles The dispersion liquid of Preparation Example 1 according to one embodiment of the present invention was dried at approximately 80 to 90°C to prepare cerium oxide particles (primary particles) in the form of powder (Sample A). Meanwhile, the cerium oxide particles used in preparing the dispersion liquids of Comparative Examples 1 to 4 were prepared respectively (Samples B1, B2, B3, and B4, respectively). Images of each of the prepared samples were taken using a TEM measuring device.
[0083] 11 to 13 are TEM images of cerium oxide particles according to one embodiment of the present invention.
[0084] 11 to 13, it was confirmed that the average particle size of the cerium oxide particles produced according to one embodiment of the present invention was approximately 4 nm or less by TEM measurement (repeated measurements were 3.9 nm, 3.4 nm, and 2.9 nm, respectively). It was confirmed that the average primary particle size of the cerium oxide particles according to one embodiment of the present invention was 4 nm or less. It was also confirmed that the cerium oxide particles had a spherical particle shape on average. Spherical cerium oxide particles with a small particle size (particle size) and a relatively uniform particle size distribution can have a wide specific surface area and are characterized by excellent dispersion stability and storage stability.
[0085] 14 to 17 show SEM images of conventional cerium oxide particles according to comparative examples.
[0086] 14 to 17, it can be seen that the conventional commercially available cerium oxide particles have particle sizes corresponding to their respective size classes, and even in the case of particles separately manufactured by a calcination method, all have primary particle sizes with an average particle size of more than 10 nm. Comparing this with the average particle size of 4 nm or less measured by TEM for the cerium oxide particles according to an embodiment of the present invention shown in Figs. 11 to 13, it can be seen that the cerium oxide particles of the conventional technology and the cerium oxide particles manufactured by a general calcination method have significantly coarser particle sizes. In contrast, it has been confirmed that the particle size (primary particle) of the cerium oxide particles of the present invention is small, and it can be predicted that the smaller the cerium oxide particle size, the more defects such as scratches that occur on the surface of the film to be polished can be reduced.
[0087] Also, Fig. 18 shows a TEM image of conventional cerium oxide particles as a comparative example. Referring to Fig. 18, it can be seen that conventional cerium oxide particles with a particle size of 10 nm or more include particles with edges and spherical particles, while conventional cerium oxide particles with a particle size of 30 nm or more are composed of angular particles with edges. In contrast, as described above, the cerium oxide particles according to the embodiments of the present invention are generally spherical in shape, whereas the cerium oxide particles of the present invention have such a spherical particle shape and a fine particle size, and therefore can include a large number of particles, thereby reducing the probability of surface defects and increasing the global flatness when polishing a silicon oxide film.
[0088] Experimental Example 2. X-ray Diffraction (XRD) Analysis of Cerium Oxide Particles The dispersion liquid of Preparation Example 1 according to one embodiment of the present application was dried at about 80 to 90°C to prepare cerium oxide particles (primary particles) in the form of powder (Sample A). The prepared Sample A was analyzed using an XRD device (Rigaku, Ultima IV). At this time, the XRD was set under the conditions of Cu Kα (λ=1.5418 Å), 40 kV, and 40 mA.
[0089] 19 is an XRD (X-ray Diffraction) pattern of the cerium oxide particles according to an embodiment of the present invention. The particle size of the cerium oxide particles obtained by analyzing the XRD pattern is shown in Table 1 below.
[0090] [Table 1]
[0091] Referring to FIG. 19 and Table 1, the XRD analysis of Sample A yielded an XRD spectrum (X-axis: 2-theta (degree scattering angle), Y-axis: signal intensity) as shown in FIG. 19. The grain size of the crystal grains calculated from the spectrum was 3.25 nm. This is similar to the TEM analysis result of Experimental Example 1, and it was confirmed that the particles of the present invention are single crystals.
[0092] Experimental Example 3. Small-angle X-ray scattering (SAXS) analysis of cerium oxide particles The particle size of the cerium oxide particles according to an embodiment of the present invention was analyzed using small angle X-ray scattering (SAXS), and the results are shown in FIG.
[0093] 20, the particle size of the cerium oxide particles according to the embodiment of the present invention is in the range of 10 nm or less with an average particle radius of 2.41 nm. This confirms that the particle size of the cerium oxide particles according to the embodiment of the present invention is much finer than that of conventional cerium oxide particles, and therefore, when a silicon oxide film is polished using the cerium oxide particles according to the embodiment of the present invention, the occurrence of defects on the surface can be further suppressed.
[0094] Experimental Example 4. Dynamic Light Scattering (DLS) Particle Size Analyzer Analysis of Cerium Oxide Particles Samples were prepared as a slurry composition of Preparation Example 2 according to an embodiment of the present application, and the slurry compositions of Comparative Examples 1, 2, 3, and 4. Each of the prepared samples was analyzed using a DLS device.
[0095] Fig. 21 shows the results of dynamic light scattering (DLS) analysis (Malvern Zetasizer Ultra) of the cerium oxide particles according to an embodiment of the present invention. Table 2 below shows the D50 values obtained by dynamic light scattering (DLS) analysis for the cerium oxide particles according to an embodiment of the present invention and the cerium oxide particles of the comparative example.
[0096] [Table 2]
[0097] 21 and Table 2, the cerium oxide particles according to the embodiment of the present invention have a secondary particle diameter D50 value of about 5.78 nm, which is measured to be less than 10 nm. This is about 148-199% of the primary particle diameter measured by TEM in Experimental Example 1 (see FIGS. 11-13), and it was confirmed that the particles hardly aggregated in the slurry, were monodispersed, and there was almost no change in particle diameter.
[0098] In contrast, the D50 particle size of cerium oxide particles of the prior art measured by dynamic light scattering (DLS) was confirmed to exceed 30 nm. Even in the case of cerium oxide particles of the 10 nm class, the D50 value of the secondary particle size measured by dynamic light scattering (DLS) was approximately 336% of the primary particle size measured by TEM. This confirms that the cerium oxide particles of the prior art have a much larger secondary particle size, resulting in a large amount of aggregation.
[0099] Therefore, it can be seen that the cerium oxide particles according to an embodiment of the present invention have lower agglomeration tendency in a slurry than the cerium oxide particles according to the comparative example of the prior art, and can be dispersed in a slurry in a more monodispersed form.
[0100] Experimental Example 5. Confirmation of the formation of cerium oxide particles by Fourier transform infrared (FT-IR) spectroscopy FIG. 22 shows the results of FT-IR spectroscopic analysis of a powder made of cerium oxide particles prepared according to an embodiment of the present invention and a powder made of ordinary cerium hydroxide particles.
[0101] As a result of analyzing the FT-IR spectrum of FIG. 22, the powder made of cerium oxide particles according to one embodiment of the present invention has a peak at 3000 cm -1 ~3600cm -1 The infrared transmittance in the range of 720 cm is about 92 to 93%. -1 ~770cm -1 It can be seen that the infrared transmittance in the range of 3000 cm is about 93 to 95%. -1 ~3600cm -1 The infrared transmittance in the range of 75 to 90% and 720 cm -1 ~770cm -1 In comparison, the infrared transmittance in the range of 3000 cm is 97-99%. -1 ~3600cm -1 The band due to the OH group of cerium hydroxide particles in the range of 720 cm appears weaker than that of normal cerium hydroxide particles, and -1 From 770cm -1 It can be seen that a peak due to Ce-O stretching is formed in the range.
[0102] Experimental Example 6. Measurement of light transmittance of slurry containing cerium oxide particles A slurry composition (sample A) was prepared in the same manner as in Production Example 2, except that the weight ratio of the cerium oxide particles in the CMP slurry was 1% by weight. Meanwhile, slurry compositions were prepared in the same manner as in Comparative Examples 1, 2, 3, and 4 (samples B1, B2, B3, and B4, respectively), except that the weight ratio of the cerium oxide particles in the CMP slurry was 1% by weight. The transmittance of each sample to light of 200 to 1100 nm was measured using a UV-Vis spectrometer (JASCO).
[0103] FIG. 23 shows the results of measuring the light transmittance of slurries containing cerium oxide particles according to an example of the present invention and conventional cerium oxide particles of Comparative Examples 1 to 4 using ultraviolet-visible (UV-vis) spectroscopy.
[0104] The cerium oxide particles according to the embodiment and the comparative example of the present invention were added to deionized water to adjust the abrasive concentration to 1.0 wt%, and CMP slurries were prepared and analyzed for light transmittance. Here, the optical spectrum was measured in the range of 200 to 1,100 nm using a UV-vis spectrophotometer (Jasco UV-vis spectrophotometer).
[0105] The transmittance (%) of Sample A and Samples B1 to B4 at wavelengths of 500 nm, 600 nm, and 700 nm in the UV-Vis analysis graph is summarized in Table 3 below.
[0106] [Table 3]
[0107] 23 and Table 3, it can be seen that the slurry containing the cerium oxide particles of the present invention has an average light transmittance of 50% or more for light having a wavelength of 450 to 800 nm, and that the light transmittance is 90% or more for light having a wavelength of about 500 nm, and 95% or more for light having wavelengths of about 600 nm and 700 nm.
[0108] In contrast, the light transmittance of slurries containing conventional cerium oxide particles according to Comparative Examples 1 to 4 (conventional cerium oxide particles of 10 nm class, 30 nm class, and 60 nm class, and ceria particles produced by a calcination method) was measured. Comparative Example 4 (calcined ceria particles) had a light transmittance of almost 0%, while the light transmittance of the slurry of Comparative Example 1 containing commercially available conventional cerium oxide particles of 10 nm class was less than 80% on average, and the light transmittance at a wavelength of 500 nm was less than 50%. In the cases of Comparative Examples 2 and 3, the particle sizes of the primary particles were also large at 30 and 60 nm, respectively, and the particle sizes of the secondary particles were also large compared to the examples of the present invention (i.e., the cohesiveness in the slurry was large), and it was found that only a transmittance of less than 20% was shown in the visible light region.
[0109] In contrast, it was confirmed that the cerium oxide particles according to one embodiment of the present invention exhibited a light transmittance of 90% or more in the visible light region, which means that the primary particles of the cerium oxide particles of the present invention are fine and are less likely to aggregate into secondary particles than the cerium oxide particles of the prior art. It is generally known that when the secondary particles exceed 20 nm, the opacity of the slurry composition can be visually observed, and the light transmittance at wavelengths in the visible light region is less than 80%.
[0110] According to the slurry composition of the present invention, the light transmittance is high and the particles can be uniformly distributed if the primary particle diameter of the cerium oxide particles is small and the tendency to aggregate into secondary particles is low. Therefore, it is easily predicted that the probability of defects such as scratches occurring on the surface will be reduced when a slurry composition containing the particles is used to polish a film to be polished.
[0111] Experimental Example 7. Peak area ratio of cerium oxide particles by XRD analysis FIG. 24 shows the intensity ratio and peak area results of XRD (X-ray Diffraction) analysis of cerium oxide particles according to one embodiment of the invention.
[0112] 24, it can be seen that the peak area of the (111) plane of the cerium oxide particles according to one embodiment of the present invention is about 496.9, and the peak area of the (200) plane is about 150.1. Here, it can be seen that the peak area ratio of the (111) plane to the (200) plane is about 3.3. When the main peaks were examined using a library, it was confirmed that the particles produced according to the embodiment of the present invention were cerium oxide particles.
[0113] Experimental Example 8. XPS analysis of cerium oxide particles 25 and 26 show the results of XPS analysis of the cerium oxide particles according to an embodiment of the present invention and the conventional cerium oxide particles of 60 nm class according to Comparative Example 3. XPS (X-ray photoelectron spectroscopy) is a method for analyzing the cerium oxide particles by irradiating them with soft X-rays. 3+ The peaks appearing at 900.2 to 902.2 eV, 896.4 to 898.4 eV, 885.3 to 887.3 eV, and 880.1 to 882.1 eV, which indicate the Ce-O bond energy, were measured, and the atomic percentage was analyzed by XPS fitting to determine the Ce content in the cerium oxide particles. 3+ and Ce 4+ The content can be measured. Table 4 below shows the XPS result data of the cerium oxide particles according to the embodiment of the present invention.
[0114] [Table 4]
[0115] From the XPS analysis results, Ce was determined according to the above-mentioned chemical formula. 3+ As a result of calculating the content, Ce 3+ It can be seen that the content is 30% or more. 3+ Since these are reactive sites, it can be seen that the polishing amount can be increased. The comparative data with conventional cerium oxide particles using the above method is shown in Table 5 below.
[0116] [Table 5]
[0117] In the case of the cerium oxide particles according to one embodiment of the present invention, as shown in Table 5, 3+ The Ce content is about 36.9 atomic %, and in Table 5, this is compared with the Ce content of conventional 60 nm class cerium oxide particles. 3+ The Ce content is less than 14 atomic %, which is higher than the 16.8% of cerium oxide particles produced by hydrothermal synthesis under supercritical or subcritical conditions with a 10 nm size as known from the conventional literature. 3+ It can be confirmed that the surface Ce content is 3+ When the content is at a high level, as in the examples of the present invention, the polishing rate on silicon-containing substrates can be increased by the chemical polishing mechanism of forming Si-O-Ce between silica and cerium.
[0118] Experimental Example 9. Analysis of cerium oxide particles by Raman spectroscopy 27 to 29 are Raman spectroscopic analysis results of cerium oxide particles according to an embodiment of the present invention, conventional cerium oxide particles of 10 nm class, and conventional cerium oxide particles of 60 nm class, respectively. As a result of the analysis, the samples of the embodiment, Comparative Example 1, and Comparative Example 3 were respectively shown in Figs. 27, 28, and 29, respectively, showing Raman spectra (X axis: Raman shift (cm -1 ), Y-axis: Counts) were derived. The analysis results of the derived Raman spectrum are shown in Table 6 below.
[0119] [Table 6]
[0120] 27 to 29 and Table 6, the conventional cerium oxide particles according to Comparative Examples 1 and 3 have a melting point of 462 cm -1The first Raman peak is around 457 cm due to vibration, whereas the cerium oxide particles according to the embodiment of the present invention have a first Raman peak around 457 cm due to vibration. -1 It can be seen that the first Raman peak is around 0.015 nm. In the case of the cerium oxide particles according to the embodiment of the present invention, the first Raman peak is around 0.015 nm. 4+ Ce 3+ It is believed that the first Raman peak shift occurs as a result of the cerium oxide particles being partially reduced to oxygen vacancies due to the induction of defects in the cubic fluorite lattice structure of the cerium oxide particles. It can also be confirmed that the intensity of the second Raman peak of the example sample is higher than that of Comparative Example 1 and Comparative Example 3 due to such a difference in particle structure.
[0121] In addition, the cerium oxide particles according to the embodiment of the present invention have a peak intensity of 457, 607, and 742 cm -1 In contrast, in the cases of Comparative Example 1 and Comparative Example 3, a peak at about 607 cm -1 The second peak is barely detectable or appears very weakly at about 742 cm -1 It was confirmed that the third peak was not detected, unlike in the examples.
[0122] Meanwhile, it was confirmed that the ratio (A / B) of the first Raman peak intensity (A) to the second Raman peak intensity (B) was 15.4, 46.0 and 66.4 for the Example, Comparative Example 1 and Comparative Example 3, respectively. As such, it was confirmed that the A / B value for the sample of the Example was much smaller than those of Comparative Examples 1 and 3. In the case of this Example, the ratio (A / C) of the first Raman peak intensity (A) to the third Raman peak intensity (C) was 50 or less, but in the cases of Comparative Examples 1 and 3, the third Raman peak was not detected and A / C could not be calculated. This is probably due to the Ce in the cerium oxide particles. 3+ This can be interpreted as a result of the increase in the oxygen vacancies due to the increase in content.
[0123] From the above results, the cerium oxide particles according to the embodiment of the present invention have a higher Ce content than the conventional cerium oxide particles according to the comparative example. 3+ It can be expected that it contains
[0124] Experimental Example 10. Electron Energy Loss Spectroscopy (EELS) Spectral Analysis of Cerium Oxide Particles The slurry composition of Production Example 2 according to one embodiment of the present invention, and the slurry compositions of Comparative Example 3 and Comparative Example 4 were each prepared as samples.
[0125] Each of the prepared samples was analyzed using an EELS measurement device. The EELS measurement was performed on the core-loss region, which is an energy loss region of 50 eV or more. Using the ionization edge observed in the core-loss region, it is possible to distinguish peaks according to the oxidation state of the sample being measured, and thus the Ce of the cerium oxide particles can be determined. 4+ The contents were quantitatively analyzed.
[0126] As a result of analyzing the samples with an EELS measurement device, EELS spectra (X-axis: binding energy (eV), Y-axis: intensity (au); signal intensity in arbitrary units) in the form shown in Figs. 30 to 32 were derived for each of the samples of Example, Comparative Examples 3, and 4, respectively.
[0127] As a result of the analysis, the EELS spectrum of the embodiment includes a first peak at about 876.5 to 886.5 eV and a second peak at 894.5 to 904.5, and the maximum intensity of the first peak is greater than the maximum intensity of the second peak. 3+ In contrast, the EELS spectra of Comparative Examples 3 and 4 show that the maximum peak intensity of the second peak is greater than the maximum peak intensity of the first peak, which is characteristic of Ce. 4+ This is because the cerium oxide particles of the embodiment have a tendency of Ce 3+The EELS spectrum of the cerium oxide particles of Comparative Examples 3 and 4 follows the trend of Ce 4+ This means that the EELS spectrum follows the trend of
[0128] Meanwhile, the EELS spectrum of the cerium oxide particles may further include a third peak section of 886.5 to 889.5 eV and a fourth peak section of 904.5 to 908.5 eV, and the peak areas of the third and fourth peak sections are determined as Ce of the cerium oxide particles. 4+ Based on the EELS spectra of Figs. 30 to 32, peak area ratios for specific binding energy ranges were derived and are shown in Tables 7 to 9 (result data for Example, Comparative Example 3, and Comparative Example 4, respectively). As a result of the EELS spectrum analysis, in the cerium oxide particles according to one embodiment of the present invention, the sum of the total EELS peak areas (P t ) to the sum of the areas of the third peak section (P1) (P1 / P t ) were calculated to be 1%, 1%, 0% and 0%, those of Comparative Example 3 were calculated to be 3%, 3%, 4% and 4%, and those of Comparative Example 4 were calculated to be 3%, 3%, 3% and 4%.
[0129] In addition, in the case of the cerium oxide particles according to an embodiment of the present invention, the sum of the entire EELS peak area (P t ) to the area ratio of the third peak area (P1) and the fourth peak area (P2) ((P1 + P2) / P t ) is about 5.8% or less on average, that of Comparative Example 3 is about 13% or more, and that of Comparative Example 4 is about 12% or more. From these results, it can be seen that the cerium oxide particles according to one embodiment of the present invention have a lower Ce content than the cerium oxide particles of Comparative Examples 3 and 4. 4+ It can be confirmed that the above formula is true.
[0130] [Table 7]
[0131] [Table 8]
[0132] [Table 9]
[0133] Experimental Example 11. XAFS (X-ray absorption fine structure) spectrum analysis of cerium oxide particles The slurry composition of Production Example 2 according to one embodiment of the present invention and the slurry composition of Comparative Example 3 were each prepared as samples.
[0134] Each of the prepared samples was analyzed using an XAFS measuring instrument. The XAFS is an analytical method in which a sample is irradiated with strong X-rays and the intensity of the absorbed X-rays is measured. The Ce in the particles was determined based on the X-ray absorption spectrum derived by measuring the light absorption coefficient (xμ) according to the X-ray energy (eV). 3+ and Ce 4+ In this case, the absorption spectrum was derived using an X-ray absorption near edge structure (XANES) method that analyzes XAFS spectra within 50 eV near the absorption edge where X-ray absorption increases sharply.
[0135] As a result of XAFS analysis for each of the samples of the Example and Comparative Example 3, XAFS spectra (X-axis: X-ray energy X (eV), Y-axis: X-ray light absorption coefficient xμ (E)) as shown in FIG. 33 and FIG. 34 were derived. As shown in FIG. 33 and FIG. 34, each of the samples of the Example and Comparative Example 3 has an absorption edge formed in the range of about 5745 to 5755 eV. On the other hand, Ce 3+ The peak (P1) where strong electronic transition occurs due to X-ray absorption by Ce is formed in the range of about 5735 to 5740 eV. 4+It was confirmed that the peak (P2), where a strong electronic transition occurs due to X-ray absorption by , is formed in the range of approximately 5745 to 5755 eV.
[0136] As a result of examining the optical absorption coefficients for P1 and P2, it can be seen that in the examples according to the present invention, the levels are about 0.1 to 0.2 and 0.5 to 0.6, respectively, whereas in the case of Comparative Example 3, the levels are less than 0.1 and more than 0.6, respectively.
[0137] Based on the analysis results, the Ce content of the samples of the embodiment and comparative example 3 was 3+ and Ce 4+ The peak areas and area ratios of the above can be confirmed as shown in Table 10 below.
[0138] [Table 10]
[0139] Referring to Table 10, the Ce on the surface of the cerium oxide particles according to one embodiment of the present invention is 3+ The area ratio of Ce on the surface of the cerium oxide particle in Comparative Example 3 is 3+ It can be seen that the area ratio is about 4 times higher than that of the conventional cerium oxide particles of the comparative example. Therefore, it can be expected that the examples of the present invention have a higher polishing rate than the conventional cerium oxide particles of the comparative example.
[0140] Experimental Example 12. UPS analysis of cerium oxide particles Cerium oxide particles according to an embodiment of the present invention and samples of Comparative Examples 3 and 4 were prepared.
[0141] 35 to 37 show the results of UPS analysis of cerium oxide particles according to an embodiment of the present invention, conventional cerium oxide particles of 60 nm size, and conventional cerium oxide particles produced by a calcination method.
[0142] Table 11 shows the work function values of the cerium oxide particles according to an embodiment of the present invention and the conventional cerium oxide particles.
[0143] In one embodiment, it was confirmed that the maximum value of the number of photoelectrons emitted per second (Counts, Y-axis) for the cerium oxide particles according to an embodiment of the present application exists in a kinetic energy range of 8 to 10 eV, whereas the maximum value exists in a kinetic energy range of 11 to 13 eV for Comparative Examples 3 and 4. From these results, it was derived that the embodiment has a work function of 3.16 eV, and Comparative Examples 3 and 4 have work functions of 2.37 eV and 2.37 eV, respectively.
[0144] In one embodiment, the UPS analysis is carried out by determining the measured kinetic energy (E kin ) value through the binding energy (E b ) and from the derived binding energy graph, the Fermi level (E F ) and the vacuum level (E cutoff Therefore, the Fermi level (E F ) and the vacuum level (E cutoff The work function φ value was calculated by applying the value of φ to the following formula 1. In this case, hv is the source energy used to emit ultraviolet light and indicates the energy of the incident light, and helium (He) was used as the source (He|UPS=21.22 eV). The work function values based on the analysis are shown in Table 11 below.
[0145] [Formula 1] φ=hv-|E f -E cutoff |
[0146] [Table 11]
[0147] Referring to Table 11, it was found that the work function value of the cerium oxide particles according to an embodiment of the present invention was the highest. As the particle size (particle size) becomes smaller, the difference in energy levels between sample orbitals becomes larger, resulting in a high energy band gap. From this, it was predicted that the particle size of the cerium oxide particles according to an embodiment of the present invention is sufficiently smaller than that of conventional cerium oxide particles, resulting in a high energy band gap, which affects the Fermi level and the vacuum level and changes the energy value of the work function. Therefore, the work function value derived by the UPS analysis indicates that the particle size of the cerium oxide particles according to an embodiment of the present invention is sufficiently smaller than that of conventional cerium oxide particles, resulting in very low cohesion. As such, the cerium oxide particles according to an embodiment of the present application, which have the characteristics of low cohesion and being monodispersed, can maximize the number of particles contacting a wafer when used in a chemical mechanical polishing slurry, thereby increasing the polishing speed of an oxide film, and can minimize defects on the wafer surface due to their fine particle size.
[0148] Experimental Example 13. BET Surface Area Analysis of Cerium Oxide Particles In order to measure the BET surface area, 1.0 g of each of the cerium oxide particle powder according to the embodiment of the present invention and the cerium oxide particle powder according to Comparative Example 1 was pretreated by degassing at 200° C. for 1 hour until the residual pressure reached a predetermined value or less, and then the amount of nitrogen gas adsorption was measured at 77 K as the relative pressure increased using a BET (Tristar II plus, Micrometrics). The BET surface area values calculated from the amount of adsorption are shown in FIGS. 38 and 39 and Table 12 below.
[0149] [Table 12]
[0150] Referring to Table 12, when typical pretreatment conditions (200° C., 1 hour) were applied, the cerium oxide particles according to the embodiment of the present invention had a BET surface area of 50 m or more when measured five times under the same conditions. 2 / g or less, whereas the powder of cerium oxide particles according to Comparative Example 1 had a BET surface area value of 80 m when measured five times under the same conditions. 2 It can be seen that the value of the comparative example is similar to the BET surface area value of 10 nm-class cerium oxide particles known from conventional literature.
[0151] From the above results, it can be seen that unlike the general tendency that the smaller the particle size, the larger the BET surface area, the powder of cerium oxide particles according to the examples of the present invention has a smaller BET surface area than the powder of cerium oxide particles of Comparative Example 1, which has a coarser particle size. This can mean that the cerium oxide particles according to the examples of the present invention have a finer particle size than conventional cerium oxide particles and can be packed more densely when powdered. Also, in the case of cerium oxide particles synthesized by a self-organizing synthesis method such as a sol-gel method or a bottom-up method, they have fewer -OH functional groups than cerium oxide particles synthesized by other synthesis methods, and therefore can be understood in the same context as the phenomenon of having smaller BET surface areas and pore volumes.
[0152] Experimental Example 14. Analysis of apparent density of cerium oxide particles Powder-form cerium oxide particles (Sample A) were prepared by drying the dispersion liquid of Preparation Example 1 according to one embodiment of the present application at about 80 to 90°C, and powder-form cerium oxide particles according to Comparative Examples 3 and 4 (Samples B and C, respectively) were prepared by drying under the same conditions. Tables 13 and 14 below show the apparent density and tap density measured for the prepared Sample A according to one embodiment of the present invention and Comparative Examples 3 and 4.
[0153] [Table 13]
[0154] [Table 14]
[0155] Referring to Table 13, the apparent density of Sample A measured by the static method was 2.22 g / ml, whereas the apparent density of the 60 nm cerium oxide particles of Comparative Example 3 was 1.90 g / ml, and the apparent density of the calcined cerium oxide particles of Comparative Example 4 was 1.30 g / ml. Referring to Table 14, the apparent density of Sample A measured by the tapping method was 2.94 g / ml, whereas the apparent density of the 60 nm cerium oxide particles of Comparative Example 3 was 2.86 g / ml, and the apparent density of the calcined cerium oxide particles of Comparative Example 4 was 1.60 g / ml, all of which are less than 2.90 g / ml. This confirms that the cerium oxide particles according to an embodiment of the present application have a finer primary particle size, yet have a larger apparent density than the cerium oxide particles of Comparative Examples having a coarser particle size. Therefore, it can be seen that the cerium oxide particles according to the embodiment of the present invention have a particle size of 10 nm or less, which is finer than conventional cerium oxide particles, but has a relatively large apparent density.
[0156] Experimental Example 15. Photoluminescence (PL) measurement analysis of dispersion containing cerium oxide particles 40 to 42 and Table 15 show the results of measuring the luminescence intensity for each of aqueous dispersions containing 1 mass % of cerium oxide particles according to an embodiment of the present invention, conventional 60 nm class cerium oxide particles, and 10 nm class cerium oxide particles produced by a calcination method. The luminescence intensity measurements were performed under the following test conditions.
[0157] (1) Test equipment: Perkin Elmer LS-55 Fluorescence Spectrometer (2) Excitation wavelength: 325 nm (3) Emission filter: 350 nm (4) Excitation slit width: 10.0 nm (5) Emission slit width: 10.0 nm
[0158] [Table 15]
[0159] 40 to 42 and Table 15, the excitation wavelength (λ excitation Fluorescence spectrometer analysis at 325 nm showed that all three samples had an excitation peak (λ 325 nm). exc ), the first emission peak at a wavelength of about 450 nm (λ ems1 ), and a second emission peak at a wavelength of about 525 nm (λ ems2 ) can be seen to indicate this.
[0160] In the case of the cerium oxide particles of the present invention, the ratio of the first emission peak to the second emission peak (λ ems1 / λ ems2 ) was found to be about 7.5, a value of 5 or more. In contrast, the conventional 10 nm-class cerium oxide particles produced by the calcination method and the commercially available 60 nm-class cerium oxide particles all had a ratio of the first emission peak to the excitation peak (λ ems1 / λ exc ) was confirmed to be more than 30, and the ratio of the first emission peak to the second emission peak (λ ems1 / λ ems2 ) was confirmed to be less than 5.
[0161] In the case of the cerium oxide particles of the present invention, Ce 3+It can be seen that the intensity of the first emission peak, which indicates that the emission intensity is smaller than that of conventional 10 nm class cerium oxide particles produced by a calcination method and commercially available 60 nm class cerium oxide particles. This is because, in the case of the cerium oxide particles of the present invention, there is very little aggregation from the dispersion to secondary particles, so light transmission is good, and therefore the emission intensity is considered to be relatively weak. Furthermore, in the case of the cerium oxide particles of the present invention, unlike conventional 60 nm class particles or cerium oxide particles produced by a calcination method, the ratio of the first emission peak to the second emission peak (λ ems1 / λ ems2 ) is 5 or more, the cerium oxide particles of the present invention have a relatively high Ce on the surface. 3+ Therefore, it can be understood from this experimental example that, in the case of the cerium oxide particles of the present invention, when used in a slurry for chemical mechanical polishing, the Ce on the particle surface is 3+ Although the content is high, the particles themselves are fine and have the characteristic of very little agglomeration in the slurry. This means that the chemical polishing rate due to the Si-O-Ce bonds between the cerium oxide particles and the oxide film substrate is increased, thereby improving the oxide film polishing rate.
[0162] Experimental Example 16. L*a*b* color system analysis of dispersion containing cerium oxide particles 43 and 44 show an aqueous dispersion containing 1 mass % of cerium oxide particles according to one embodiment of the present invention, and an aqueous dispersion containing 1 mass % of conventional 60 nm class cerium oxide particles.
[0163] Tables 16 and 17 show a summary of the chromaticity values, expressed in the L*a*b* color system, for a dispersion containing 1% by mass of cerium oxide particles according to one embodiment of the present invention, and a dispersion containing 1% by mass of conventional 60 nm class cerium oxide particles.
[0164] In one embodiment, the analysis of the L*a*b* color system was performed using a CM-5 (KONICA MINOLTA, JAPAN) according to ASTM E1164 (Standard practice for obtaining spectrometric data for object color evaluation), using a Xenon lamp D65 as a light source, in the wavelength range of 360 to 740 nm, with wavelength intervals of 10 nm. The analysis results are shown in Tables 16 and 17 below.
[0165] [Table 16]
[0166] [Table 17]
[0167] 43 and 44, it can be seen with the naked eye that the aqueous dispersion containing the cerium oxide particles of the present invention has a yellowish color, while the aqueous dispersion containing the conventional 60 nm class cerium oxide particles is opaque but appears closer to white.
[0168] In addition, referring to Tables 16 and 17, it can be seen that in the case of the dispersion containing 1% by weight of cerium oxide particles according to an embodiment of the present invention, the average L* value is about 99.7, the average a* value is about -5.9, and the average b* value is about 11.7. In contrast, in the case of the dispersion containing conventional cerium oxide particles of 60 nm, the average L* value is about 94.7, the average a* value is about -2.2, and the average b* value is about 0.1. Therefore, the cerium oxide particle dispersion according to the present invention satisfies the range of L* value of 95 or more and b* value of 10 to 25, and it can be seen that the cerium oxide particle dispersion according to the present invention has fine particle characteristics because of the larger L* value compared to the conventional cerium oxide particle dispersion of 60 nm, and it can be interpreted that the cerium oxide particle dispersion according to an embodiment of the present invention has a higher yellowness because of the larger b* value. When the cerium oxide particles according to an embodiment of the present application are used in an aqueous dispersion containing the cerium oxide particles, the respective values are within the above-mentioned ranges when expressed in the L*a*b* color system, and the yellowness is particularly high. This means that the cerium oxide particles are very fine and monodispersed, and the Ce on the surface of the cerium oxide particles is dispersed. 3+ This can be interpreted as meaning that the content is relatively very high.
[0169] Experimental Example 17. Sedimentation rate of cerium oxide particles during centrifugation A slurry composition containing 1.0 wt % of cerium oxide particles according to an example of the present application, and slurry compositions containing 1.0 wt % of cerium oxide particles according to Comparative Example 1 and Comparative Example 3 were each prepared as samples.
[0170] The sample was centrifuged using a high speed centrifuge or an ultra high speed centrifuge (Supra R22 (model name), manufactured by Hanil Science Industrial Co. Ltd, Korea) while varying the centrifugal force from 2100G, 3300G, 4265G, 26188G, and 398282G under conditions starting from a slurry composition temperature of 25°C. The settling rates of the cerium oxide particles at this time are shown in Table 18 below.
[0171] [Table 18]
[0172] Referring to Table 18, it can be seen that when a slurry composition containing 1.0 wt% of each cerium oxide particle is centrifuged, the settling rate of the cerium oxide particles according to an embodiment of the present invention is lower than the settling rates of the cerium oxide particles according to Comparative Examples 1 and 3 under the same conditions. For example, when centrifuged for 30 minutes at a centrifugal force of 4,265G, the embodiment of the present invention exhibits a settling rate of 0 wt%, whereas Comparative Example 1 exhibits a settling rate of 27.14 wt%, and Comparative Example 3 already exhibits a settling rate of 96.9 wt% when centrifuged for 10 minutes at a smaller centrifugal force of 3,300G. Therefore, this may mean that the particle size of the primary particles and / or secondary particles of the cerium oxide particles according to the examples of the present invention is finer than the particle size of the cerium oxide particles of Comparative Examples 1 and 3, and may also mean that they are monodispersed. Therefore, since the monodispersed particles come into contact with the wafer in the chemical mechanical polishing process, the number of contacting particles increases, improving the oxide film polishing rate. Furthermore, it may mean that when polishing is performed using a slurry composition containing the cerium oxide particles according to the examples of the present invention, the occurrence rate of polishing defects such as scratches on the polished wafer can be reduced.
[0173] Experimental Example 18. Analysis of remaining amount of cerium oxide precursor An evaluation was performed to measure the amount of residual precursors in the CMP slurry containing cerium oxide particles prepared in Preparation Example 2. The slurry sample of Preparation Example 2 was prepared in powder form through a process of drying at high temperature until a powder was obtained, and the residual powder was dissolved again in pure water. The precursor content in the solution dissolved in pure water was analyzed by ICP-MS and converted into a weight ratio of cerium oxide powder, and it was confirmed that substances such as basic substances, solvents, and ammonia were hardly detected, and were 300 ppm or less. More specifically, hardly detected means that the amount is significantly less than the unit of PPM or less, or is not contained at all. Therefore, since the cerium oxide particles are appropriately distributed inside the slurry and hardly contain cerium precursors, basic substances, and other impurities that may be generated due to the characteristics of the wet process, it was expected that the cerium oxide particles according to one embodiment of the present application do not need to be redispersed in the slurry solvent through a separate separation or grinding process after being prepared in the form of a dispersion liquid by a wet process.
[0174] [Table 19]
[0175] Experimental Example 19. Comparison of oxide film polishing rates of cerium oxide particles The slurry composition of Production Example 2 according to one embodiment of the present application, and the slurry compositions of Comparative Example 1 and Comparative Example 3 were each prepared as samples.
[0176] The oxide wafer using the sample was polished using a polisher (Reflexion® LK CMP, Applied Materials). Specifically, a PE-TEOS silicon oxide wafer (300 mm PE-TEOS Wafer) was placed on a platen, and the surface of the wafer was brought into contact with a polisher pad (IC1010, DOW). Then, the sample slurry composition was supplied at a rate of 200 mL / min, and the platen and the polisher pad were rotated to perform a polishing process. At this time, the rotation speed of the platen and the rotation speed of the head were 67 rpm / 65 rpm, the polishing pressure was 2 psi, and the polishing time was 60 seconds. Meanwhile, the silicon oxide thin film thickness of the wafer was measured using ST5000 (Spectra Thick 5000ST, K-MAC). The results are shown in Table 20 below.
[0177] [Table 20]
[0178] As shown in Table 20, when the slurry composition of the embodiment is used, the silicon oxide film removal rate is about 6 times faster than that of the slurry compositions of Comparative Examples 1 and 3. This is because the cerium oxide particles contained in the slurry composition of the embodiment have a small particle size, so the number of particles that effectively act in polishing is large compared to the content, and the Ce on the surface is removed. 3+ This is presumably because the content (molar ratio and / or weight ratio) is high, which increases the chemical reactivity with the silicon oxide film surface.
[0179] Experimental Example 20. Evaluation of defects in cerium oxide particles 45 and 46 are scanned images of an oxide wafer before and after CMP using a CMP slurry composition including cerium oxide particles according to one embodiment of the present invention and a CMP slurry composition including 60 nm cerium oxide particles.
[0180] The surface analysis of the oxide wafer was carried out by full wafer scan using an AIT-XP instrument.
[0181] 45 and 46, the surface of an oxide wafer subjected to CMP using the CMP slurry composition containing cerium oxide particles according to the embodiment of the present invention was analyzed before and after CMP. The number of defects before CMP was 6 and the number of defects after CMP was 1. This confirms that the number of defects on the oxide wafer surface was reduced after CMP using the embodiment of the present invention, and no scratches were generated during the CMP process. In contrast, the surface of an oxide wafer subjected to CMP using the CMP slurry composition containing cerium oxide particles according to the prior art was analyzed before and after CMP. The number of defects before CMP was 34, but the number of defects after CMP increased to 64. This confirms that the cerium oxide particles according to the prior art caused scratches on the surface of the wafer. This suggests that the particle size of the cerium oxide particles according to the embodiment of the present invention is smaller than that of the cerium oxide particles according to the prior art, and therefore the probability of defects on the surface of the oxide wafer to be polished is significantly reduced.
[0182] Experimental Example 21. Analysis of behavior of oxide film polishing rate and oxide film / polysilicon film polishing selectivity by adding cationic polymer The cerium oxide particles prepared according to an embodiment of the present application and conventional commercially available cerium oxide particles of 60 nm class were added to deionized water, the pH was adjusted to 5.8, and then a cationic polymer was added as shown in Table 21 below. Under the same polishing conditions as in Experimental Example 19, the polishing rate (Å / min) of the oxide film and the polishing rate (Å / min) of the polysilicon film were measured.
[0183] [Table 21]
[0184] Referring to Table 21, it was confirmed that the polishing rate of the silicon oxide film was significantly decreased when 0.01 wt % of a cationic polymer was added to the slurries using commercially available 60 nm class cerium oxide particles in Comparative Examples 2 to 8. In contrast, it was confirmed that the polishing rate of the oxide film was increased by the inclusion of a cationic polymer in the slurries containing cerium oxide particles of the present invention, as shown in the results of Examples 2 to 8 in Table 21. This is a feature not seen in CMP slurries using conventional cerium oxide particles.
[0185] Furthermore, comparing Example 1 in Table 21 with Examples 2 to 8 containing cationic polymers, it was confirmed that the polishing speed of the silicon oxide film increased while the polishing speed of the polysilicon film decreased significantly, and that the polishing selectivity of the oxide film / polysilicon film was in the range of about 200 to 900 and not more than 2000.
[0186] Furthermore, the behavior of the oxide film polishing rate (Å / min) was investigated by gradually increasing the content of the cationic polymer in the samples of the embodiment and comparative example in Table 21. Figure 47 shows the result of measuring the behavior of the oxide film polishing rate depending on the addition of the cationic polymer to a CMP slurry composition including cerium oxide particles according to one embodiment of the present invention.
[0187] 47 and Table 21, it was observed that the polishing rate of the CMP slurry of the present invention increases as the content of the cationic polymer increases, whereas in the case of the conventional ceria slurry, the polishing rate gradually decreases as the concentration continues to increase to 0.001% or more. This is because in the case of the conventional wet ceria slurry, the cationic polymer is added simply to act as a pH buffer to stabilize the particles, and therefore increasing the content of the cationic polymer may interfere with the polishing process of the abrasive particles. In contrast, in the case of the CMP slurry of the present invention, the cationic polymer not only stabilizes the particles but also acts as a polishing accelerator.
[0188] [Mode for carrying out the invention]
[0189] The present invention may, however, be embodied in many different forms and should not be construed as limited to the embodiments set forth herein but only as defined by the claims which follow.
[0190] In addition, the terms used in the present invention are merely used to describe specific embodiments and are not intended to limit the present invention. A singular expression includes a plural expression unless otherwise clearly indicated in the context. Throughout the specification of this application, when a certain component is described as "including", this does not mean that other components are excluded, and means that other components may be further included, unless otherwise specified.
[0191] The term "monodisperse" used in the present invention means that when cerium oxide particles are dispersed in a slurry, aggregation into secondary particles is suppressed and the particle size of the primary particles is relatively maintained, which may mean that the particle size (D50) of the secondary particles measured by dynamic light scattering (DLS) is 3.0 times or less, 2.8 times or less, 2.5 times or less, 2.2 times or less, 2.0 times or less, or preferably 1.9 times or less of the particle size of the primary particles measured by TEM. In addition, when considering the particle size distribution, etc., it does not exclude the inclusion of unavoidable impurities of a relatively coarse size.
[0192] The term "transparent" as used in the present invention means that when cerium oxide particles are dispersed in a slurry, the slurry composition is observed to be transparent when confirmed by visual inspection, and more specifically means that the average light transmittance for light in the visible light region is 50% or more, preferably 70% or more, and more preferably 80% or more. This further means that the cerium oxide particles of the present invention are inhibited from agglomerating into secondary particles and relatively maintain the particle size of the primary particles.
[0193] A polishing composition can be characterized according to its polishing rate (i.e., removal rate) and its planarization efficiency. The polishing rate refers to the rate at which material is removed from the surface of a substrate, and is usually expressed in units of length (thickness) per unit time (e.g., angstrom (Å) / min). Specifically, a polishing surface, such as a polishing pad, must first contact the "high point" of the surface and remove material to form a flat surface. A process that achieves a flat surface with less material removal is considered to be more efficient than a process that requires more material removal to achieve flatness.
[0194] Often, the removal rate of silicon oxide patterns can be rate limiting for the dielectric polishing step in STI processes, and therefore a high removal rate of silicon oxide patterns is favorable for increasing device throughput, but if the blanket removal rate is too fast, over-polishing of oxide in exposed trenches will lead to trench erosion and increase device defects.
[0195] The present invention will be described in detail below.
[0196] A first aspect of the present invention provides cerium oxide particles for chemical mechanical polishing, characterized in that, in an aqueous dispersion in which the content of the cerium oxide particles is adjusted to 1.0 wt %, the light transmittance for light with a wavelength of 500 nm is 50% or more.
[0197] Hereinafter, the cerium oxide particles for chemical mechanical polishing according to one aspect of the present application will be described in detail.
[0198] FIG. 1 shows an oxide film removal mechanism according to an embodiment of the present invention. As shown in FIG. 1, Ce is deposited on the surface of a cerium oxide particle. 3+ If the ions are not activated, they cannot react smoothly with SiO2.
[0199] In one embodiment of the present application, the particle size of the cerium oxide particles may be measured by X-ray diffraction (XRD) analysis (primary particles). In one embodiment of the present application, the particle size of the cerium oxide particles measured by X-ray diffraction (XRD) analysis may be 11 nm or less. In other embodiments, the thickness may be 10.8 nm or less, 10.5 nm or less, 10.2 nm or less, 10 nm or less, 9.5 nm or less, 9.0 nm or less, 8.5 nm or less, 8.0 nm or less, 7.5 nm or less, 7.0 nm or less, 6.5 nm or less, 6.0 nm or less, 5.5 nm or less, 5.0 nm or less, 4.5 nm or less, or 4.0 nm or less, or may be 0.3 nm or more, 0.5 nm or more, 0.7 nm or more, 1.0 nm or more, 1.1 nm or more, 1.2 nm or more, 1.3 nm or more, 1.4 nm or more, 1.5 nm or more, 1.6 nm or more, 1.7 nm or more, 1.8 nm or more, 1.9 nm or more, 2.0 nm or more, 2.1 nm or more, 2.2 nm or more, 2.3 nm or more, or 2.4 nm or more. If the particle size of the cerium oxide particles is less than 0.3 nm, the crystallinity may decrease, and the polishing rate for the target film may be excessively hindered, resulting in a decrease in polishing efficiency, whereas if the particle size exceeds 11 nm, a large number of surface defects such as scratches may occur. In one embodiment of the present application, the average particle size of the cerium oxide particles measured by the X-ray diffraction (XRD) analysis may be 0.5 to 10 nm, preferably 1 to 10 nm, and more preferably 2 to 9 nm.
[0200] In another embodiment of the present application, the particle size of the cerium oxide particles may be measured by a transmission electron microscope (TEM) (primary particles). In one embodiment of the present application, the particle size of the cerium oxide particles measured by a transmission electron microscope (TEM) may be 11 nm or less. In other embodiments, the thickness may be 10.8 nm or less, 10.5 nm or less, 10.2 nm or less, 10 nm or less, 9.5 nm or less, 9.0 nm or less, 8.5 nm or less, 8.0 nm or less, 7.5 nm or less, 7.0 nm or less, 6.5 nm or less, 6.0 nm or less, 5.5 nm or less, 5.0 nm or less, 4.5 nm or less, or 4.0 nm or less, or may be 0.3 nm or more, 0.5 nm or more, 0.7 nm or more, 1.0 nm or more, 1.1 nm or more, 1.2 nm or more, 1.3 nm or more, 1.4 nm or more, 1.5 nm or more, 1.6 nm or more, 1.7 nm or more, 1.8 nm or more, 1.9 nm or more, 2.0 nm or more, 2.1 nm or more, 2.2 nm or more, 2.3 nm or more, or 2.4 nm or more. If the particle size of the cerium oxide particles is less than 0.3 nm, the crystallinity may decrease, and the polishing rate for the target film may be excessively hindered, resulting in a decrease in polishing efficiency, whereas if the particle size exceeds 11 nm, a large number of surface defects such as scratches may occur. In one embodiment of the present application, the average particle size of the cerium oxide particles measured by the transmission electron microscope (TEM) may be 0.5 to 10 nm, preferably 1 to 10 nm, and more preferably 2 to 9 nm.
[0201] In another embodiment of the present application, the particle size of the cerium oxide particles may be measured by a small angle X-ray scattering (SAXS) method (primary particles). In one embodiment of the present application, the particle size of the cerium oxide particles measured by a small angle X-ray scattering (SAXS) method may be 15 nm or less. In other embodiments, the thickness may be 14 nm or less, 13 nm or less, 12 nm or less, 11 nm or less, 10 nm or less, 9.5 nm or less, 9.0 nm or less, 8.5 nm or less, 8.0 nm or less, 7.5 nm or less, 7.0 nm or less, 6.5 nm or less, 6.0 nm or less, 5.5 nm or less, 4.5 nm or less, or 4.0 nm or less, or may be 0.3 nm or more, 0.5 nm or more, 0.7 nm or more, 1.0 nm or more, 1.1 nm or more, 1.2 nm or more, 1.3 nm or more, 1.4 nm or more, 1.5 nm or more, 1.6 nm or more, 1.7 nm or more, 1.8 nm or more, 1.9 nm or more, 2.0 nm or more, 2.1 nm or more, 2.2 nm or more, 2.3 nm or more, or 2.4 nm or more. If the particle size of the cerium oxide particles is less than 0.3 nm, the crystallinity may decrease, and the polishing rate for the target film may be excessively hindered, resulting in a decrease in polishing efficiency, whereas if the particle size exceeds 15 nm, a large number of surface defects such as scratches may occur. In one embodiment of the present application, the average particle size of the cerium oxide particles measured by the small angle X-ray scattering (SAXS) method may be 0.5 to 15 nm, preferably 1 to 12 nm, and more preferably 1.5 to 10 nm.
[0202] In one embodiment of the present application, the particle size of the cerium oxide particles in the slurry may be measured by dynamic light scattering (DLS) analysis (secondary particles). The dynamic light scattering analysis may be performed using analytical equipment known to those of ordinary skill in the art, preferably using an Anton Parr particle size analyzer or a Malvern Zetasizer Ultra, but these are merely non-limiting examples and are not intended to be limiting.
[0203] In one embodiment of the present application, the particle size of the cerium oxide particles measured by a dynamic light scattering (DLS) particle size analyzer may be 1 to 30 nm. In another embodiment of the present application, the particle size may be 29 nm or less, 27 nm or less, 25 nm or less, 23 nm or less, 22 nm or less, 20.8 nm or less, 20.5 nm or less, 20.2 nm or less, 20 nm or less, 19.8 nm or less, 19.5 nm or less, 19.2 nm or less, 18 nm or less, 17 nm or less, or 15 nm or less, or 1.2 nm or more, 1.4 nm or more, 1.5 nm or more, 1.8 nm or more, 2 nm or more, 3 nm or more, or 4 nm or more. If the particle size of the secondary particles exceeds the above range, it means that the primary particles are largely aggregated in the slurry composition, and in this case, it is difficult to determine that the slurry is monodispersed. If the particle size of the secondary particles is less than the above range, the polishing speed for the target film may be excessively hindered, and the polishing efficiency may be reduced.
[0204] In an embodiment of the present application, the cerium oxide particles may be characterized in that they satisfy the following Equation 2, where a is the particle size of the cerium oxide particles measured using a dynamic light scattering (DLS) particle size analyzer and b is the particle size of the cerium oxide particles measured using a transmission electron microscope (TEM):
[0205] [Formula 2] a≦2.2b
[0206] Such a characteristic is an index showing that the cerium oxide particles of the present invention have low cohesion when dispersed in a slurry. If the coefficient b exceeds 2.2, it means that a lot of cohesion occurs in the slurry, which may mean that the particle size becomes coarse, making it difficult to suppress defects on the wafer surface during polishing.
[0207] In another embodiment of the present application, the cerium oxide particles may be characterized in that, when a is a particle size of the cerium oxide particles measured by a dynamic light scattering (DLS) particle size analyzer and b is a particle size of the cerium oxide particles measured by a small angle X-ray scattering (SAXS) method, the particle size satisfies the following Equation 3:
[0208] [Formula 3] a≦2.5b
[0209] Such a characteristic is an index showing that the cerium oxide particles of the present invention have low cohesion when dispersed in a slurry. When the coefficient b exceeds 2.5, it means that a lot of cohesion occurs in the slurry, which may mean that the particle size becomes coarse, making it difficult to suppress defects on the wafer surface during polishing.
[0210] In one embodiment of the present application, Ce on the surface of the cerium oxide particles 3+ The content can be analyzed using XPS, for example, theta probe base system manufactured by Thermo Fisher Scientific Co. Ce on the surface of the cerium oxide abrasive particles can be used. 3+ The content can be expressed by the following chemical formula 1.
[0211] [Chemical formula 1] Ce 3+ Content (%)=(Ce 3+ Peak area) / [(Ce 3+ Peak area) + (Ce 4+ Peak area)]
[0212] In one embodiment, when X-ray photoelectron spectroscopy (XPS) is performed on the surface of the cerium oxide particles, Ce 3+ In particular, when X-ray photoelectron spectroscopy (XPS) is performed on the surface of the cerium oxide particles, XPS peaks showing Ce-O bond energies appear at 900.2 to 902.2 eV, 896.4 to 898.4 eV, 885.3 to 887.3 eV, and 880.1 to 882.1 eV. 3+ XPS peaks indicating Ce—O bond energies may appear as a first peak at 900.2 to 902.2 eV, a second peak at 896.4 to 898.4 eV, a third peak at 885.3 to 887.3 eV, and a fourth peak at 880.1 to 882.1 eV.
[0213] In one embodiment of the present application, the area of the first peak may be 3% or more, or 4% or more, the areas of the second peak and the fourth peak may be 5% or more, 7% or more, or 10% or more, respectively, relative to the total XPS peak area, and the area of the third peak may be 4% or more, 5% or more, or 6% or more.
[0214] In addition, in an embodiment of the present disclosure, when an X-ray photoelectron spectroscopy (XPS) analysis is performed, the Ce-O bond energy on the surface of the cerium oxide particles is analyzed. 3+ In another embodiment of the present invention, the ratio of the sum of the XPS peak areas showing the Ce-O bond energy on the surface of the cerium oxide particles to the sum of the XPS peak areas showing the Ce-O bond energy on the surface of the cerium oxide particles may be 0.29 to 0.70. 3+ The ratio of the sum of the XPS peak areas indicating the Ce-O bond energy is 0.18 or more, 0.19 or more, 0.192 or more, 0.195 or more, 0.198 or more, 0.20 or more, 0.202 or more, 0.205 or more, 0.208 or more, 0.21 or more, 0.22 or more, 0.24 or more, 0.25 or more, 0.27 or more, 0.28 or more, 0.30 or more, 0.32 or more, or 0.35 or more. The cerium oxide particles may have a surface area of 0.90 or less, 0.88 or less, 0.85 or less, 0.83 or less, 0.80 or less, 0.77 or less, 0.75 or less, 0.72 or less, 0.71 or less, 0.705 or less, 0.70 or less, 0.695 or less, 0.69 or less, 0.68 or less, 0.67 or less, 0.66 or less, 0.65 or less, 0.64 or less, 0.63 or less, 0.62 or less, 0.61 or less, or 0.60 or less. 3+ will not be able to exist, making it difficult to expect a sufficient increase in the polishing rate of the oxide film, and when the amount exceeds the above range, it may be difficult to interpret the cerium oxide particles as existing, taking into account the oxidation number.
[0215] That is, in one embodiment of the present disclosure, when X-ray photoelectron spectroscopy (XPS) is performed, Ce is present on the surface of the cerium oxide particles for chemical mechanical polishing. 3+may be contained at 18 atomic % or more, 19 atomic % or more, 20 atomic % or more, 22 atomic % or more, 24 atomic % or more, 25 atomic % or more, 27 atomic % or more, 28 atomic % or more, 30 atomic % or more, 32 atomic % or more, or 35 atomic % or more, or may be contained at 90 atomic % or less, 88 atomic % or less, 85 atomic % or less, 83 atomic % or less, 80 atomic % or less, 77 atomic % or less, 75 atomic % or less, 72 atomic % or less, or 70 atomic % or less.
[0216] In the case of cerium oxide particles according to an embodiment of the present application, Ce on the particle surface 3+ This is presumably due to the fact that the particle synthesis process is carried out in the liquid phase under acidic conditions using a wet process, and thus the Ce content on the particle surface is high. 3+ When the content is relatively high, the oxide film removal rate can be improved.
[0217] In one embodiment of the present application, the cerium oxide particles according to one embodiment of the present invention have a Ce on the particle surface, which distinguishes them from conventional abrasive particles. 3+ The cerium oxide particles may be characterized by having two or more Raman peaks in the Raman spectrum, which indicates that the cerium oxide particles are present in a large amount.
[0218] In one embodiment of the present application, the cerium oxide particles have a diameter of 455 cm -1 ~460cm -1 In another embodiment, the cerium oxide particles may have a first Raman peak in the band range of 586 cm -1 ~627cm -1 In yet another embodiment, the cerium oxide particles may have a second Raman peak in the band range of 712 cm -1 ~772cm -1 In this case, the band range may refer to the numerical range of the Raman shift, which is the X-axis of the Raman spectrum.
[0219] In an embodiment of the present application, the cerium oxide particles may be characterized in that the ratio (A / B) of the first Raman peak intensity (A) to the second Raman peak intensity (B) is 35 or less. The ratio A / B is preferably 30 or less, more preferably 25 or less, and even more preferably 20 or less. The lower limit of the ratio A / B is not particularly limited, but may be 5 or more, 10 or more, or 15 or more. The second Raman peak is Ce 3+ This can be interpreted as a Raman shift caused by an increase in the ratio of oxygen vacancies as the content increases. Therefore, the smaller the intensity ratio (A / B), the more the Ce of the cerium oxide particles. 3+ This may mean that the content increases, which may suggest that the polishing rate may be improved when using the cerium oxide particles according to the embodiments of the present invention, despite the particle size being finer than that of conventional cerium oxide particles, by promoting the chemical polishing action using the Si-O-Ce bond with the oxide film wafer.
[0220] In an embodiment of the present application, the cerium oxide particles may be characterized in that a ratio (A / C) of the first Raman peak intensity (A) to the third Raman peak intensity (C) is 50 or less. The A / C may be preferably 45 or less, more preferably 43 or less. The lower limit of the A / C is not particularly limited, and may be 5 or more, 10 or more, or 15 or more.
[0221] As described above, the cerium oxide particles according to an embodiment of the present disclosure have a higher Ce content than conventional cerium oxide particles. 3+ Since the cerium oxide particles have a high content, it is possible to provide a slurry composition that has a superior polishing rate compared to the content of cerium oxide particles, despite its small particle size, and also to suppress the occurrence of polishing scratches.
[0222] In one embodiment of the present application, Ce on the surface of the cerium oxide particles 3+ In relation to the content, it can be analyzed using electron energy loss spectroscopy (EELS) spectrum, for example, 2 or more, Ce 4+The oxide can be characterized by having an EELS peak indicative of an oxidation state indicative of
[0223] The cerium oxide particles (and / or a slurry composition containing the same) can exhibit EELS spectra such as those shown in FIGS.
[0224] The EELS spectrum of the cerium oxide particles according to one embodiment of the present application may be characterized in that it includes a first peak at 876.5 to 886.5 eV and a second peak at 894.5 to 904.5 eV, and the maximum intensity of the first peak is greater than the maximum intensity of the second peak. 3+ A higher content may mean that the EELS spectrum is more similar to that of trivalent cerium oxide.
[0225] In an embodiment of the present application, the spectrum may further include a third peak at 886.5 to 889.5 eV and a fourth peak at 904.5 to 908.5 eV. In the case of the third and fourth peaks, peaks can be divided according to the oxidation state. 4+ By determining the area of the peak section appearing due to the oxidation state of the cerium oxide particles of the present invention, it is possible to distinguish between the cerium oxide particles of the present invention and conventional cerium oxide particles.
[0226] In one embodiment of the present application, the sum of the total areas of the peaks in the spectrum (P t ) to the sum of the areas of the third peak section (P1) (P1 / P t ) may be 0.025 or less, more preferably 0.024 or less, 0.022 or less, 0.018 or less, 0.015 or less, 0.012 or less, 0.011 or less, or 0.01 or less. In contrast, conventional cerium oxide particles exhibit a minimum value of 0.03 or more, and such a feature will be demonstrated by the following experimental examples.
[0227] In one embodiment of the present application, the sum of the total areas of the peaks in the spectrum (P tThe ratio of the sum of the areas of the third peak section (P1) and the sum of the areas of the fourth peak section (P2) to the sum of the areas of the third peak section (P1) and the fourth peak section (P2) ((P1+P2) / P t ) may be 0.1 or less. The area ratio may be preferably 0.099 or less, 0.098 or less, 0.096 or less, 0.095 or less, 0.094 or less, 0.092 or less, or 0.090 or less. The ratio of the cerium oxide particles according to one embodiment of the present application may mean, for example, an average ratio of values measured n times when the same sample is measured n times. The area ratio ((P1+P2) / P t ) may be, for example, 0.01 or more, 0.012 or more, 0.014 or more, 0.016 or more, or 0.018 or more. When the area ratio is 0.1 or less, the Ce content on the surface of the cerium oxide particle relative to the entire cerium oxide content is 3+ It can mean that the content is high, and the higher the Ce content, the 3+ The content of this compound can promote the chemical polishing action due to the Si-O-Ce bond on the silicon oxide film, thereby increasing the polishing rate.
[0228] The cerium oxide particles according to one embodiment of the present application have Ce on the particle surface, which distinguishes them from conventional abrasive particles. 3+ The cerium oxide particles may be characterized by having two or more peaks in the XAFS spectrum, which indicates that the component is contained in a large amount.
[0229] In one embodiment of the present application, the cerium oxide particles (and / or a slurry composition including the same) may exhibit XAFS spectra as shown in FIG. 9 and FIG.
[0230] In an embodiment, the cerium oxide particles may have a maximum optical absorption coefficient of a first peak in a range of 5730 eV to 5740 eV in an XAFS spectrum measurement, and the first peak may be Ce 3+ It may also be one which shows an oxidation state of
[0231] In yet another embodiment, the cerium oxide particles may have a maximum optical absorption coefficient of a second peak in a range of 5740 eV to 5760 eV in an XAFS spectrum measurement, and the second peak may be Ce 4+ It may also be one which shows an oxidation state of
[0232] In one embodiment of the present application, the maximum optical absorption coefficient (maximum value of the peak) of the first peak may be 0.1 to 0.4. In another embodiment of the present application, the maximum optical absorption coefficient of the first peak may be 0.11 or more, 0.12 or more, 0.13 or more, 0.14 or more, 0.15 or more, 0.2 or more, or 0.25 or more, or 0.38 or less, 0.35 or less, 0.32 or less, or 0.30 or less.
[0233] In one embodiment, the maximum optical absorption coefficient (maximum value of the peak) of the second peak may be less than 0.6. In another embodiment, the maximum optical absorption coefficient of the second peak may be 0.11 or more, 0.12 or more, 0.13 or more, 0.14 or more, 0.15 or more, 0.2 or more, or 0.25 or more, or 0.58 or less, 0.55 or less, 0.52 or less, or 0.50 or less.
[0234] When the optical absorption coefficient of the first peak is less than 0.1 and when the optical absorption coefficient of the second peak is more than 0.6, Ce is 3+ This means that the weight is reduced, which may mean that the polishing rate may be further hindered.
[0235] In one embodiment of the present application, the ratio (A1 / A2) of the area of the first peak (A1) to the area of the second peak (A2) in the XAFS spectrum may be 0.03 or more. The peak area ratio (A1 / A2) may be 0.03 or more, 0.05 or more, 0.07 or more, 0.09 or more, or 0.1 or more, more preferably 0.11 or more, and even more preferably 0.12 or more. That is, the Ce according to the XAFS (X-ray absorption fine structure) spectrum may be3+ The areas of the peaks A3 and Ce 4+ For the sum of the areas A4 of the peaks showing Ce 3+ The ratio of the areas of the peaks A3 (A3 / (A3 + A4) may be 0.1 or more (10% or more). When the weight ratio is less than 0.03, the Ce on the surface of the cerium oxide particles is 4+ Compared to the Ce content 3+ If the content is insufficient, the polishing rate may decrease.
[0236] In an embodiment of the present application, the cerium oxide particles may be subjected to photoelectron spectroscopy, specifically, ultraviolet photoelectron spectroscopy (UPS) using light in the UV region. Photoelectron spectroscopy techniques are traditionally divided into X-ray photoelectron spectroscopy (XPS) using single-wavelength light in the X-ray region and ultraviolet photoelectron spectroscopy (UPS) using light in the UV region. XPS is a technique for investigating the type, chemical state, concentration, etc. of elements in a sample by analyzing electrons emitted mainly from the core level of atoms inside the sample using X-rays having an energy of about 1000 to 1500 eV, and many commercial equipments are available, and the analytical method and usage are widely known, whereas UPS is a technique for investigating various states that electrons directly participating in chemical bonds can have in a solid by emitting electrons in the valence electron region of the sample using light in the extreme UV region of about 10 to 20 eV. In particular, the so-called angle-resolved UPS (ARUPS / ARPES) can directly measure the band structure of single crystal samples, and can be used to understand the physical properties of high-temperature superconductors and colossal magnetoresistance materials, where such measurements are an important factor in understanding the unique properties of materials. When a solid sample is irradiated with light with energy hv, the electrons gain kinetic energy while satisfying the laws of conservation of energy and momentum. The value of the kinetic energy of the electrons that leave the sample at this time is given by:
[0237] E kin =hv-φ-|E b |
[0238] Here, E kin is the kinetic energy of the emitted electron, φ is the work function of the sample, E bis the binding energy when the emitted electron is bound to the sample. If the intensity due to the kinetic energy of the emitted electron is measured from the outside using an electron energy analyzer, the density of states due to the binding energy of the electrons inside the sample can be grasped. Therefore, referring to the above equation, the binding energy can be derived from the measured kinetic energy. At this time, the work function φ of the sample is calculated by the hv value of the source energy and the Fermi level (E F ) and the vacuum level (E cutoff ) can be expressed as
[0239] φ=hv-|E f -E cutoff |
[0240] When the UPS results are plotted on a graph, the zero on the x-axis is the Fermi level (E F ), and E cutoff is a value expressed by the vacuum level. hv is the source energy used to emit ultraviolet light, which indicates the energy of the incident light. Generally, helium (He) is used as the source.
[0241] In one embodiment of the present application, the band structure of the cerium oxide may vary depending on the grain size (particle size), and as the grain size (particle size) decreases, the difference in energy levels between the sample orbitals increases, resulting in a high energy band gap. Conversely, as the grain size increases, the difference in energy levels decreases, resulting in a low energy band gap. Thus, as described above, as the grain size decreases, the energy gap between the valence band and the conduction band increases, resulting in a lower Fermi level (E F ) and the vacuum level can be changed to increase the energy (eV) of the derived work function.
[0242] In an embodiment of the present application, the cerium oxide particles may be characterized in that the maximum number of photoelectrons (Counts) emitted per second during UPS analysis is in a range of kinetic energy of 10 eV or less. This characteristic is in contrast to conventional ceria particles. The maximum number of photoelectrons (Counts) emitted per second may be in a range of kinetic energy of 6 to 10 eV or 7 to 10 eV, and preferably in a range of 8 to 10 eV.
[0243] In an embodiment of the present application, the cerium oxide particles may have a work function value measured by UPS in the range of 2.5 eV or more. The work function value may be preferably in the range of 2.7 eV or more, and more preferably in the range of 3.0 eV or more. The upper limit of the work function value is not particularly limited, and may be less than 10 eV, 9 eV or less, or 8 eV or less. The fact that the work function value satisfies the above range means that the particle size of the cerium oxide particles dispersed in the slurry is small, which indicates that the cohesion is very small, as compared with conventional cerium oxide particles. Since the cerium oxide particles according to an embodiment of the present application have such characteristics of small cohesion and monodispersion, when used in a chemical mechanical polishing slurry, the number of particles in contact with the wafer can be maximized, and the oxide film polishing speed can be increased, and at the same time, the particle size itself is fine, so that defects on the wafer surface can be minimized.
[0244] In one embodiment of the present application, when the specific surface area of 1 g of the powder made of cerium oxide particles is measured, the BET surface area value is 50 m 2 In another embodiment, the BET surface area value is 49 m 2 / g or less, 48m 2 / g or less, 47m 2 / g or less, 46m 2 / g or less, 45m 2 / g or less, 44m 2 / g or less, 43m 2 / g or less, preferably 42m2 / g or less. This shows a different tendency from conventional cerium oxide particles, which have a larger BET surface area value as the particle size becomes smaller. This can be inferred to be because cerium oxide particles synthesized by self-organizing synthesis methods such as the sol-gel method and the bottom-up method have a smaller specific surface area and pore volume than cerium oxide particles manufactured by other synthesis methods, and in particular, the ratio of -OH functional groups present on the surface of the cerium oxide particles is low. In addition, when the particles are analyzed by BET under the same conditions of 1.0 g of powder, the powder sample is aligned at a higher density than the conventional cerium oxide particles according to Comparative Example 1, and it can be predicted that the measured BET surface area value will be smaller. Therefore, it can be confirmed that the cerium oxide particles according to the embodiments of the present invention have a finer particle size than the conventional cerium oxide particles of 10 nm class according to Comparative Example 1, but have a smaller BET surface area value than the cerium oxide particles according to Comparative Example 1. The above results indicate that the cerium oxide particles according to the embodiments of the present invention have a finer particle size and at the same time, have Ce on the particle surface when compared with the conventional cerium oxide particles. 4+ and the content of -OH functional groups compared to Ce 3+ This can be seen in the same context as the tendency to show surface chemical properties with a high content.
[0245] In one embodiment of the present application, the cerium oxide particles may have an apparent density, as measured by a static method, of 2.00 to 5.00 g / ml, preferably 2.00 to 4.00 g / ml, and more preferably 2.00 to 3.00 g / ml.
[0246] In another embodiment of the present application, the cerium oxide particles may have an apparent density, as measured by a Tab method, of 2.90 to 5.00 g / ml, preferably 3.00 to 5.00 g / ml, and more preferably 3.20 to 5.00 g / ml.
[0247] When a slurry in which cerium oxide particles having an apparent density of more than 5.00 g / ml are dispersed in water is used for polishing, scratches may occur on the polished surface due to the particle size of the coarse primary and secondary particles. In addition, in one embodiment of the present application, when cerium oxide particles having a particle size of less than 2.00 g / ml are used, the polishing rate becomes extremely small as the particle size of the primary particles decreases, so that sufficient polishing effect may not be obtained. Therefore, it is preferable to maintain an apparent density of 2.00 g / ml or more even if the particle size is small, such as 10 nm or less. Therefore, it can be seen that the cerium oxide particles according to one embodiment of the present invention have a relatively high apparent density compared to conventional cerium oxide particles, despite their fine particle size, and are different. It is expected that such characteristics may have a certain effect on the polishing rate of the oxide film.
[0248] In one embodiment of the present application, when photoluminescence (PL) is measured at a wavelength of 325 nm based on an aqueous dispersion containing 1.0 wt % cerium oxide particles, the maximum intensity of the first peak (λ1) at a wavelength of 435 to 465 nm is in the range of 0.1 to 30, 0.2 to 20, 0.3 to 10, or 0.5 to 7. In the case of conventional coarse cerium oxide particles available on the market, the maximum peak intensity exceeds 30 under the same conditions, but the cohesion in the slurry is strong, which may mean that stronger luminescence occurs rather than transmission.
[0249] In one embodiment of the present application, based on an aqueous dispersion in which the content of the cerium oxide particles is adjusted to 1.0 wt %, the maximum intensity of the second peak (λ2) at a wavelength of 510 to 540 nm may be in the range of 0.1 to 10, 0.1 to 7.5, 0.1 to 5, or 0.1 to 3. In the case of conventional commercially available coarse cerium oxide particles, the maximum peak intensity exceeds 10 under the same conditions, but the cohesion in the slurry is also strong, which may mean that stronger emission occurs rather than transmission.
[0250] In one embodiment of the present application, the cerium oxide particles are dispersed in water at a content of 1.0 wt % and the photoluminescence (PL) intensity is measured at a wavelength of 325 nm to understand the characteristics of the particles. Specifically, in one embodiment of the present application, when a fluorescence spectrometer is used at an excitation wavelength of 325 nm, an excitation peak (λ exc ) appears at a wavelength of 435 to 465 nm, a first peak (λ1) appears at a wavelength of 435 to 465 nm, and a second peak (λ2) appears at a wavelength of 510 to 540 nm. The excitation peaks indicate peaks at the excitation wavelength, and the first peak is Ce. 3+ The second peak indicates Ce. 4+ This could be interpreted as indicating
[0251] In one embodiment of the present invention, when the photoluminescence (PL) intensity is measured at a wavelength of 325 nm for an aqueous dispersion containing 1.0 wt % of the cerium oxide particles, the excitation peak (λ exc ) to the intensity ratio of the first peak (λ1) at wavelengths of 435 to 465 nm (λ1 / λ exc ) may be less than 30, preferably 27 or less, 25 or less, more preferably 23 or less, even more preferably 18 or less, 15 or less, and even more preferably 10 or less.
[0252] In one embodiment of the present application, the intensity ratio (λ1 / λ2) of the first peak (λ1) to the second peak (λ2) at a wavelength of 510 to 540 nm may be 4 or more, preferably 5 or more, more preferably 5.5 or more, and even more preferably 6 or more, and may be 20 or less, preferably 18 or less, more preferably 15 or less, even more preferably 12 or less, and even more preferably 10 or less.
[0253] The cerium oxide particles according to an embodiment of the present disclosure have the excitation peak (λ exc ) to the intensity ratio of the first peak (λ1) (λ1 / λ exc) and the intensity ratio (λ1 / λ2) of the first peak (λ1) to the second peak (λ2) are within the above ranges, the surface of the cerium oxide particle has a high content of Ce. 3+ Although it contains Ce, there is very little aggregation into secondary particles in the dispersion liquid, and it has the characteristic of providing good light transmission. 3+ It can be seen that the content of cerium oxide particles of the present invention is relatively high. When the particles are used in a slurry for chemical mechanical polishing, the Ce content on the particle surface is relatively high. 3+ Although the content is high, the particles themselves are fine and there is very little agglomeration in the slurry. As a result, the chemical polishing rate due to the Si-O-Ce bonds between the cerium oxide particles and the oxide film substrate is increased, and the oxide film polishing rate is improved.
[0254] In one embodiment of the present application, the yellowness of the dispersion containing the cerium oxide particles can be evaluated by the L*a*b* color system, where L*a*b is defined by the CIE1976 L*a*b* color space established by the CIE (Commission Internationable de Eclairage: International Commission on Illumination) in 1976. This color space is a color space having quantities L*, a*, and b* in a rectangular coordinate system determined by the following equation:
[0255] L*=116(Y / Y0) 1 / 3 -16 a*=500[(X / X0) 1 / 3 -(Y / Y0) 1 / 3 ] b*=200[(Y / Y0) 1 / 3 -(Z / Z0) 1 / 3 ] (where X / X0, Y / Y0, Z / Z0>0.008856, X, Y, and Z are the tristimulus values of the object color, and X0, Y0, and Z0 are the tristimulus values of the light source that illuminates the object color, and are standardized to Y0=100.
[0256] L* indicates brightness and is also called the "lightness index." Furthermore, a* and b* indicate hue and saturation, and are also called the "chromaticness index." In the L*a*b* color system, the higher the L* value, the closer the color is to white, and the smaller the L* value, the closer the color is to black. The larger the a* value is on the + side, the stronger the reddish color, and the smaller it is (the larger it is on the - side), the stronger the greenish color. Furthermore, the larger the b* value is on the + side, the stronger the yellowish color, and the smaller it is (the larger it is on the - side), the stronger the blueish color. Furthermore, when both the a* and b* values are 0, it means the color is achromatic.
[0257] In one embodiment of the present application, when the color of the aqueous dispersion in which the content of the cerium oxide particles is adjusted to 1.0 wt % is expressed in the L*a*b* color system, the L* value may be 80 or more, preferably 85 or more, more preferably 90 or more, even more preferably 95 or more, and even more preferably 98 or more. If the L* value is smaller than the above range, it may mean that the particle growth of the cerium oxide abrasive particles has progressed too much, and there are many coarse particles that cause defects in the wafer during polishing. The L* value may be 100 or less, more preferably 99.9 or less.
[0258] In one embodiment of the present application, the b* value may be 8 or more, preferably 10 or more, more preferably 11 or more, and may be less than 30, preferably 25 or less, more preferably 20 or less, and even more preferably 15 or less. If the b* value is smaller than the above range, a necessary chemical reaction may not be obtained during polishing, and fine irregularities on the polishing surface may not be polished smoothly.
[0259] In one embodiment of the present application, the a* value may be less than -3, preferably -4 or less, more preferably -5 or less, and may be in the range of -8 or more, more preferably -7 or more.
[0260] Therefore, when the color of an aqueous dispersion containing 1.0 wt % cerium oxide particles is expressed in the L*a*b* color system, if each value is within the above range, the dispersion can be observed as a yellow transparent state, and it is estimated that the deeper the yellowness of the dispersion, the higher the polishing speed. In particular, the cerium oxide particles according to one embodiment of the present application, despite their fine particle size, can effectively remove Ce from the cerium oxide surface when included in a slurry for chemical mechanical polishing. 3+ The high ratio of Ce on the surface of the cerium oxide particles makes it possible to extremely quickly remove the oxide film, and the fine particles can minimize defects on the wafer surface. When expressed in the L*a*b* color system, the respective values are within the above ranges, or the yellowness is particularly high, which means that the Ce on the surface of the cerium oxide particles is higher than that of conventional cerium oxide particles. 3+ This can be interpreted as meaning that the ratio of
[0261] In one embodiment, when an aqueous dispersion containing 1.0 wt% of cerium oxide particles is centrifuged at a centrifugal force of 4265G (6,000 rpm) for 30 minutes, the sedimentation rate of the cerium oxide particles may be 25 wt% or less. In another embodiment, the sedimentation rate may be 20 wt% or less, 15 wt% or less, 10 wt% or less, or more preferably 5 wt% or less.
[0262] In one embodiment, when an aqueous dispersion containing 1.0 wt% cerium oxide particles is centrifuged at a centrifugal force of 2100G (3,200 rpm) for 10 minutes, the sedimentation rate of the cerium oxide particles may be 0.6 wt% or less. In another embodiment, the sedimentation rate may be 0.55 wt% or less, 0.5 wt% or less, 0.45 wt% or less, or more preferably 0.4 wt% or less.
[0263] In another embodiment of the present application, when an aqueous dispersion containing 1.0 wt% cerium oxide particles is centrifuged at a centrifugal force of 3,300 G (4,000 rpm) for 30 minutes, the sedimentation rate of the cerium oxide particles may be 5.0 wt% or less, or 4.8 wt% or less, 4.5 wt% or less, 4.2 wt% or less, or more preferably 4.0 wt% or less.
[0264] In another embodiment of the present application, when an aqueous dispersion containing 1.0 wt% of cerium oxide particles is centrifuged at a centrifugal force of 26,188 G (12,000 rpm) for 30 minutes, the sedimentation rate of the cerium oxide particles may be 45.0 wt% or less, or 42 wt% or less, 40 wt% or less, 38 wt% or less, or more preferably 35 wt% or less.
[0265] In another embodiment of the present application, when an aqueous dispersion containing 1.0 wt% of cerium oxide particles is centrifuged at a centrifugal force of 39282 G (18,000 rpm) for 30 minutes, the sedimentation rate of the cerium oxide particles may be 90.0 wt% or less, or 80 wt% or less, 70 wt% or less, 65 wt% or less, or more preferably 60 wt% or less.
[0266] In one embodiment of the present application, the aqueous dispersion may have a liquid viscosity of 0.3 to 2.0 mPa·s, 0.5 to 1.8 mPa·s, 0.55 to 1.5 mPa·s, or 0.6 to 1.2 mPa·s, and in a preferred embodiment, the centrifugation may be performed under a condition of 0.65 to 1.2 mPa·s.
[0267] In this way, when the settling rate of the cerium oxide particles is within the above-mentioned range when centrifuged under each of the conditions from weak centrifugal force to severe centrifugal force, it can be understood that the cerium oxide particles according to one embodiment of the present invention have a finer particle size than conventional cerium oxide particles and are monodispersed. Therefore, since the monodispersed particles come into contact with the wafer in the chemical mechanical polishing process, the number of contacting particles increases, which is expected to improve the oxide film polishing speed. It can also be seen that when polishing is performed using an embodiment of the present invention having a fine particle size, the occurrence of polishing defects can be reduced.
[0268] In one embodiment of the present application, the cerium oxide primary particles may have one or more shapes selected from the group consisting of a spherical shape, a cube shape, a tetragonal shape, an orthorhombic shape, a rhombohedral shape, a monoclinic shape, a hexagonal shape, a triclinic shape, and a cuboctahedron shape, and are preferably spherical particles.
[0269] In an embodiment of the present application, the cerium oxide particles may be manufactured by a method of growing particles through chemical synthesis, preferably a bottom-up method. The cerium oxide particles may be synthesized by a method such as, but not limited to, a sol-gel method, a supercritical reaction, a hydrothermal reaction, or a co-precipitation method. The bottom-up method is a type of chemical synthesis that has been attracting attention in recent years, and is a method of growing starting materials such as atoms or molecules into nanometer-sized particles through a chemical reaction.
[0270] In one embodiment of the present application, the polishing composition includes wet cerium oxide particles. The wet cerium oxide particles may be any suitable wet cerium oxide particles. For example, the wet cerium oxide particles may be precipitated cerium oxide particles, including colloidal cerium oxide particles, or polycondensed cerium oxide particles.
[0271] In one embodiment of the present application, the wet cerium oxide particles also preferably have defects on the surface of the particles. Without wishing to be bound to any particular theory, milling of cerium oxide particles can result in defects on the surface of the cerium oxide particles, and such defects also affect the performance of the cerium oxide particles in chemical mechanical polishing compositions. In particular, the cerium oxide particles can be fractured during milling, exposing less favorable surface states. This process is known as relaxation, and atoms around the surface of the cerium oxide particles that have limited ability to reorganize and return to more favorable states cause defects to form on the particle surface.
[0272] In one embodiment of the present application, in the generation of secondary particles of an abrasive, each solvent has a unique dielectric constant value, and the dielectric constant of the solvent affects the aggregation and growth of nuclei by changing the surface energy and surface charge in nucleation and crystal growth during powder synthesis, which affects the size and shape of the powder. The dielectric constant of the solvent and the surface potential (zeta potential) of the particles dispersed in the solvent are proportional to each other, and if the zeta potential is low, the surface repulsive force between fine particles or between nuclei generated by reaction is small, resulting in an unstable state, and aggregation between fine particles or between nuclei may occur at a very high speed. In this case, the magnitude of the surface repulsive force is about the same between fine particles or between nuclei, so aggregation of uniform size is possible. The secondary particles thus aggregated grow into relatively large particles through particle merging processes such as strong aggregation of primary fine particles and nuclei and Oswald ripening depending on reaction conditions such as temperature and concentration.
[0273] A second aspect of the present invention provides a slurry composition for chemical mechanical polishing, comprising: cerium oxide particles; and a solvent; and wherein, in an aqueous dispersion in which the content of the cerium oxide particles is adjusted to 1.0 wt %, the composition has a light transmittance of 50% or more for light with a wavelength of 500 nm.
[0274] Detailed descriptions of parts that overlap with the first aspect of the present application will be omitted, but the contents described with respect to the first aspect of the present application may be similarly applied to the second aspect even if the description is omitted.
[0275] The chemical mechanical polishing slurry composition according to the second aspect of the present application will be described in detail below.
[0276] A slurry composition for chemical mechanical polishing according to an embodiment of the present disclosure includes cerium oxide particles and a solvent.
[0277] In one embodiment of the present application, the cerium oxide particles contained as abrasive particles in the slurry may have a positive zeta potential value, preferably a zeta potential value of 1 to 80 mV, 5 to 60 mV, or 10 to 50 mV in a pH range of 2 to 8. When the zeta potential value of the cerium oxide particles is positive and the polarity of the silicon oxide film surface is negative, the polishing efficiency can be increased due to the attractive force between the cerium oxide particles and the surface of the silicon oxide film.
[0278] In one embodiment of the present application, the cerium oxide particles have a lower hardness than silica particles or alumina particles, but due to a chemical polishing mechanism in which Si-O-Ce bonds are formed between silica and cerium, the polishing rate for silicon-containing surfaces such as glass and semiconductor substrates is very high, which is advantageous for polishing semiconductor substrates.
[0279] In one embodiment of the present application, the content of the precursor material in the slurry composition may be 300 ppm or less by weight. In another embodiment of the present application, the content of the precursor material in the slurry composition may be 200 ppm or less, 150 ppm or less, 100 ppm or less, 75 ppm or less, 50 ppm or less, 25 ppm or less, 15 ppm or less, 10 ppm or less, 7.5 ppm or less, 5 ppm or less, 2.5 ppm or less, 2 ppm or less, 1.75 ppm or less, 1.5 ppm or less, 1.25 ppm or less, 1 ppm or less, 0.75 ppm or less, or 0.5 ppm or less by weight. The slurry composition may be substantially free of the precursor material. Here, the precursor material may mean a precursor material used and generated in the process of producing cerium oxide particles in a wet process, such as a cerium precursor material, a basic material, a solvent, and ammonia.
[0280] In one embodiment of the present disclosure, the slurry composition for chemical mechanical polishing may include 5 wt% or less of the cerium oxide particles based on the total weight of the composition. In another embodiment of the present disclosure, the slurry composition for chemical mechanical polishing may include 4 wt% or less, 3 wt% or less, 2 wt% or less, 1.5 wt% or less, 1 wt% or less, 0.8 wt% or less, 0.5 wt% or less, 0.4 wt% or less, 0.3 wt% or less, less than 0.2 wt% or less, less than 0.2 wt%, 0.19 wt% or less, 0.15 wt% or less, 0.12 wt% or less, 0.10 wt% or less, 0.09 wt% or less, or 0.07 wt% or less of the cerium oxide particles based on the total weight of the composition, or 0.001 wt% or more, or 0.001 wt% or more. The slurry composition for chemical mechanical polishing of the present invention may be characterized in that, even when a slurry having the same polishing rate is used, a smaller amount of cerium oxide particles is added relative to the total weight of the slurry composition for chemical mechanical polishing, and yet a high oxide film polishing efficiency can be achieved.
[0281] In one embodiment of the present invention, the aqueous dispersion containing cerium oxide particles at a content of 1.0 wt% may have an average light transmittance of 50% or more or 60% or more for light having a wavelength of 450 to 800 nm, preferably 70% or more, more preferably 80% or more, and even more preferably 90% or more. In another embodiment of the present application, the optical transmittance of the aqueous dispersion may be 50% or more, 55% or more, 60% or more, 65% or more, 70% or more, 75% or more, or 80% or more for light having a wavelength of 500 nm. The optical transmittance of the aqueous dispersion may be 75% or more, 80% or more, 85% or more, or 90% or more for light having a wavelength of 600 nm. The optical transmittance of the aqueous dispersion may be 87% or more, 90% or more, 93% or more, or 95% or more for light having a wavelength of 700 nm. The light transmittance value of the slurry composition satisfies the above range, which may mean that the particle size of the primary particles of the cerium oxide particles according to an embodiment of the present invention is small and that the secondary particle aggregation is less than that of conventional ceria particles. With such low aggregation, the particles can be uniformly distributed due to high dispersion stability, and the number of particles in contact with the wafer is increased, resulting in a high oxide film polishing rate, and since the particles themselves are fine, it can be easily estimated that when a film to be polished is polished using a slurry composition containing the particles, the probability of defects such as scratches on the surface is reduced. In other words, in the case of cerium oxide particles with a primary particle size of 10 nm or less, the higher the light transmittance in the visible light region, the better the silicon oxide film polishing rate can be predicted.
[0282] In one embodiment of the present application, when the powder made of the cerium oxide particles is subjected to Fourier-transformation infrared (FT-IR) spectroscopy, a peak at 3000 cm in the spectrum determined by the FT-IR spectroscopy is -1 ~3600cm -1 In the above range, the infrared transmittance of the powder made of cerium oxide particles may be 90% or more, or 100% or less, 97% or less, or 95% or less. -1~770cm -1 In the above range, the infrared transmittance of the powder may be 96% or less, and may be 85% or more, 88% or more, more preferably 90% or more, and further preferably 92% or more. -1 ~3600cm -1 In the range of 720 cm in the FT-IR spectrum of the powder made of cerium oxide particles according to one embodiment of the present application, the infrared transmittance having a value in the above range may mean that the band due to the OH group is relatively weak, which indicates a difference from the FT-IR spectrum of the powder made of cerium hydroxide particles. -1 ~770cm -1 The presence of a peak showing infrared transmittance in the range may mean that Ce-O stretching occurs in the range, which may mean that the particles produced according to one embodiment of the present invention exhibit the properties of cerium oxide particles.
[0283] In one embodiment of the present application, the chemical mechanical polishing slurry composition may have a pH of 10 or less, preferably 1 to 9, 1 to 8, or 2 to 7, from the viewpoint of dispersion stability and polishing efficiency. More specifically, if the pH is less than 1, the removal rate of silicon oxide film may decrease sharply and undesirable polishing characteristics may be exhibited, and if the pH is more than 10, undesirable polishing characteristics may be exhibited or the pH stability and dispersion stability may decrease, causing aggregation, which may result in the generation of microscratches and defects.
[0284] In one embodiment of the present application, the chemical mechanical polishing slurry composition may include one or more acid or base pH adjusters and buffers that can adjust the pH in consideration of the final pH of the composition, polishing rate, polishing selectivity, etc. As the pH adjuster for adjusting the pH, one that can adjust the pH without affecting the properties of the chemical mechanical polishing slurry composition can be used. In one embodiment of the present application, the pH adjuster may be an acidic pH adjuster or a basic pH adjuster for achieving an appropriate pH.
[0285] In one embodiment of the present application, examples of the pH adjusting agent include one or more inorganic acids selected from the group consisting of sulfuric acid, hydrochloric acid, nitric acid, and phosphoric acid; one or more organic acids selected from the group consisting of acetic acid, citric acid, glutaric acid, glucolic acid, formic acid, lactic acid, malic acid, malonic acid, maleic acid, oxalic acid, phthalic acid, succinic acid, and tartaric acid; one or more amino acids selected from the group consisting of lysine, glycine, alanine, arginine, valine, leucine, isoleucine, methionine, cysteine, proline, histidine, phenylalanine, serine, tricine, tyrosine, aspartic acid, tryptophan, and aminobutyric acid; imidazole; alkylamines; alcoholamines; quaternary amine hydroxides; ammonia; or combinations thereof. In particular, the pH adjusting agent may be triethanolamine, tetramethylammonium hydroxide (TMAH or TMAOH), or tetraethylammonium hydroxide (TEAH or TEA-OH). Examples of the pH adjuster include at least one selected from the group consisting of ammonium methyl propanol (AMP), tetramethyl ammonium hydroxide (TMAH), potassium hydroxide, sodium hydroxide, magnesium hydroxide, rubidium hydroxide, cesium hydroxide, sodium bicarbonate, sodium carbonate, triethanolamine, tromethamine, and niacinamide. Preferably, the pH adjuster may be triethanolamine or aminobutyric acid.
[0286] In one embodiment of the present application, the solvent may be any solvent used in a slurry composition for chemical mechanical polishing, for example, deionized water, but the present invention is not limited thereto. Also, preferably, ultrapure water may be used. The content of the solvent may be the remaining amount excluding the content of the cerium oxide particles and other additional additives, based on the entire slurry composition for chemical mechanical polishing. In one embodiment of the present application, the solvent may include water (e.g., deionized water) as an aqueous carrier and one or more water-miscible organic solvents. Examples of usable organic solvents may include alcohols (e.g., propenyl alcohol, isopropyl alcohol, ethanol, 1-propanol, methanol, 1-hexanol, etc.); aldehydes (e.g., acetylaldehyde, etc.); ketones (e.g., acetone, diacetone alcohol, methyl ethyl ketone, etc.); esters (e.g., ethyl formate, propyl formate, ethyl acetate, methyl acetate, methyl lactate, butyl lactate, ethyl lactate, etc.); sulfoxides (e.g., dimethyl sulfoxide (DMSO)); ethers (e.g., tetrahydrofuran, dioxane, diglyme, etc.); amides (e.g., N,N-dimethylformamide, dimethylimidazolidinone, N-methylpyrrolidone, etc.); polyhydric alcohols and their derivatives (e.g., ethylene glycol, glycerol (glycerin), diethylene glycol, diethylene glycol monomethyl ether, etc.); and nitrogen-containing organic compounds (e.g., acetonitrile, amylamine, isopropylamine, dimethylamine, etc.).
[0287] In one embodiment of the present application, the polishing composition optionally further comprises one or more other additives. The polishing composition may further comprise surfactants and / or rheology modifiers, including thickeners and coagulants (e.g., polymeric rheology modifiers such as urethane polymers), biocides (e.g., KATHON TMLX), etc. Suitable surfactants include, for example, cationic surfactants, anionic surfactants, anionic polyelectrolytes, nonionic surfactants, amphoteric surfactants, fluorinated surfactants, mixtures thereof, and the like.
[0288] In one embodiment of the present disclosure, the chemical mechanical polishing slurry composition has excellent dispersion stability, and is characterized by a high polishing rate for silicon oxide film.
[0289] The chemical mechanical polishing slurry composition may be provided in the form of a one-part slurry composition containing all components such as cerium oxide particles, a solvent, and other additives, or, if necessary, in the form of a two-part or three-part slurry composition in which the components are stored in two or more containers and then mixed at or near the time of use. The selection of such a form of provision and the combination of the stored components are within the knowledge of those skilled in the art, and the overall polishing characteristics and polishing rate can be adjusted by changing the mixing ratio.
[0290] In one embodiment of the present application, the chemical mechanical polishing slurry composition has a silicon oxide film polishing rate of 1,000 Å / min or more, preferably 2,000 Å / min or more, and more preferably 3,000 Å / min or more. Basically, the higher the oxide film polishing rate, the better, and there is no particular upper limit, but the silicon oxide film polishing rate may be preferably 10,000 Å / min or less, 9,000 Å / min or less, 8,000 Å / min or less, 7,000 Å / min or less, 6,000 Å / min or less, or 5,000 Å / min or less. In particular, in the case of a chemical mechanical polishing slurry composition using cerium oxide particles according to one embodiment of the present application, even when the content of cerium oxide particles is low, the particle size (particle size) is small, so that the number of particles contained is large and the surface Ce is high compared to a slurry composition containing conventional cerium oxide particles. 3+ The Si-O-Ce bond increases depending on the content, and this can significantly improve the polishing rate of the silicon oxide film.
[0291] In an embodiment of the present application, the chemical mechanical polishing slurry composition may have an oxide / polysilicon polishing selectivity of 50 or more, 100 or more, 150 or more, or 200 or more, and may have an oxide / polysilicon polishing selectivity of 3,000 or less, 2,000 or less, 1,500 or less, 1,000 or less, 900 or less, or 800 or less. In the case of the oxide / polysilicon selectivity, it cannot be excluded that a selectivity of 3,000 or more may be achieved by appropriately adjusting the content of the cationic polymer.
[0292] When the cerium oxide is used as an abrasive, unlike mechanical polishing which removes only the hydrated layer formed on the surface, the high reactivity of cerium oxide and silicon oxide causes a chemical bond of Si-O-Ce, and the cerium oxide removes the silicon oxide lumps on the surface of the silicon oxide film by peeling them off, thereby polishing the silicon oxide film. In addition, the cerium oxide powder according to the embodiment of the present invention has a small particle size and therefore low strength, which has the advantage of providing excellent wide-area flatness during polishing and also solving the problem of micro-scratches formed by large particles.
[0293] Another aspect of the present invention provides a slurry composition for chemical mechanical polishing, comprising: cerium oxide particles; a solvent; and a cationic polymer.
[0294] In one embodiment of the present disclosure, the oxide film polishing rate may be increased depending on the content of the cationic polymer, which is a major technical feature of the present invention compared to the conventional technology, and will be described in detail below.
[0295] In one embodiment of the present application, the cationic polymer may play two roles in the chemical mechanical polishing slurry composition of the present invention. First, the cationic polymer may act as a stabilizer for the slurry composition and as a pH buffer to ensure particle dispersibility and dispersion stability. In addition, the cationic polymer of the present invention may act as an oxide film polishing accelerator. In conventional polishing slurries, cationic polymers are added to improve dispersion stability or used to protect field oxide during step removal, and in order to obtain these properties, it is necessary to sacrifice a part of the oxide film polishing rate. In contrast, the cationic polymer added to the polishing slurry of the present invention not only improves dispersion stability, but also increases the overall oxide film polishing rate as the amount of cationic polymer added increases.
[0296] In one embodiment of the present application, the content of the cationic polymer may be 0.001 wt% or more, 0.002 wt% or more, 0.003 wt% or more, 0.004 wt% or more, or 0.005 wt% or more, or 1 wt% or less, 0.5 wt% or less, 0.1 wt% or less, 0.05 wt% or less, 0.03 wt% or less, or 0.01 wt% or less, based on the total weight of the slurry composition for chemical mechanical polishing. If the content of the cationic polymer is less than 0.001% based on the total weight of the slurry composition for chemical mechanical polishing, the content is too low to fully function as a polishing accelerator and to affect the polishing rate. On the contrary, if the content exceeds 1%, the added cationic polymer may interfere with the polishing process of cerium oxide, and may reduce the polishing rate.
[0297] In an embodiment of the present application, the cationic polymer may be a polymer or copolymer containing an amine group or an ammonium group. For example, in an embodiment of the present disclosure, the cationic polymer may be polydiallyldimethyl ammonium chloride, polyallylamine, polyethyleneimine, polydiallylamine, polypropyleneimine, polyacrylamide-co-diallydimethyl ammonium chloride, polyacrylamide, or a combination thereof, and preferably, polydiallyldimethyl ammonium chloride, polyallylamine, polyethyleneimine, polyacrylamide-co-diallydimethyl ammonium chloride, polyacrylamide, poly(trimethylammonio ethyl methacrylate), ... The polymer may be characterized as being a dimethylamine / methacrylate, a dicyandiamide-diethylenetriamine copolymer, a diallyldimethylamine / hydrochloride-acrylamide copolymer, a dicyandiamide-formaldehyde copolymer, or a combination thereof.
[0298] A third aspect of the present invention provides a method for manufacturing a semiconductor device, comprising the step of polishing with the above-mentioned slurry composition for chemical mechanical polishing.
[0299] Detailed descriptions of parts that overlap with the first and second aspects of the present application will be omitted, but the contents described for the first and second aspects of the present application may be similarly applied to the third aspect even if the description is omitted.
[0300] The method for manufacturing a semiconductor device according to the third aspect of the present application will now be described in detail.
[0301] First, a shallow trench isolation (STI) routine process will be described. Among processes for planarizing an insulating film, photolithography, etching, and polishing can be classified as basic processes that are commonly applied.
[0302] The process begins with the photo process, which is the first step to separate the elements. The photo process is carried out using an auxiliary device called a track and an exposure machine that exposes the wafer to light to transfer the circuit pattern (mask). First, a photoresist is applied. Since the photoresist has high viscosity, it is applied thinly onto the insulating film while the wafer is rotating. The applied photoresist must be of a uniform height so that the photoresist depth is appropriate. If the photoresist depth is not sufficient during exposure, photoresist residues will remain during development, and the underlying film (insulating layer) will not be sufficiently removed during the subsequent etching process. After exposure, the wafer is returned to the track device and a development process is carried out to remove the exposed parts.
[0303] As the second step, STI etching is a process of removing the insulating layer (oxide layer + nitride layer) directly below the developed portion (the portion where the photoresist film has been removed) and a part of the substrate. The etching process can be a dry or wet process. Dry (dry) etching is usually a method of digging down using a plasma state. Compared to wet (liquid) methods, dry methods can be advantageous in shaping the trench by digging down without etching the side walls (anisotropic etching). In this case, since overetching may occur, it may be necessary to accurately calculate the etching end point before proceeding. Residues remain after etching, which can be dealt with.
[0304] After the trench shape is etched, the photosensitive layer is no longer useful and can be removed by ashing. In the ashing process, preferably plasma can be used, which allows high accuracy ashing. The shape of the semiconductor element up to the ashing process is shown in FIG. 2.
[0305] According to an embodiment of the present disclosure, a method for manufacturing a semiconductor device may include simultaneously polishing a silicon oxide layer, a silicon nitride layer, and a polysilicon layer using the chemical mechanical polishing slurry composition.
[0306] 2 to 6 are cross-sectional views illustrating a method for manufacturing a semiconductor device according to an embodiment of the present application.
[0307] 2, a trench 13 may be formed in an upper film 11 on a lower film 10. For example, an upper film 11 may be formed on the lower film 10, and a nitride film (polishing stop film) 12 may be formed on the upper film 11. The lower film 10 may include a film of any material. For example, the lower film 10 may be an insulating film, a conductive film, a semiconductor film, or a semiconductor wafer (substrate). The upper film 11 may include an insulating film (oxide film), a conductive film, a semiconductor film, or a combination thereof.
[0308] When the upper film 11 includes a plurality of stacked insulating films, the insulating films may be of the same type or different types. For example, the upper film 11 may include a silicon oxide film and a silicon nitride film that are alternately and repeatedly stacked. The upper film 11 may further include a semiconductor film and a lower insulating film below the silicon oxide film and the silicon nitride film. For example, the lower insulating film may be disposed below the semiconductor film.
[0309] The nitride film (polishing stop film) 12 may be formed to have a relatively large thickness (e.g., 100 Å to 4,000 Å) by depositing, for example, silicon nitride (e.g., SiN), polysilicon, metal nitride (e.g., TiN), metal, etc. The trench 13 may be formed by an etching process or a drilling process. The trench 13 may have a depth that penetrates the nitride film (polishing stop film) 12 and the upper film 11 to reach the lower film 10. For example, the trench 13 may have a depth sufficient to expose the lower film 10.
[0310] Referring to FIG. 3, STI can form a double oxide film. First, before filling the trench 13 with an insulating material, a liner oxide film is thinly covered as a first insulating film 14 by a diffusion method. This is believed to be to allow the second insulating film to be well formed on the silicon substrate using CVD deposition in the subsequent step. According to another embodiment of the present application, when filling the trench 13 by high density plasma CVD (HDPCVD), it can also play a role in preventing damage from plasma containing high energy. According to another embodiment of the present application, the first insulating film (liner oxide film) can be formed into a thin film such as a gate oxide film by injecting oxygen gas into a diffusion furnace and heating it to a high temperature. According to another embodiment of the present application, a nitride film can be used instead of an oxide film.
[0311] Referring to FIG. 4, a first insulating film 14 and a second insulating film 15 filling the trench 13 may be formed by depositing a plurality of insulating materials. The first insulating film 14 and the second insulating film 15 may have different densities and deposition rates. According to an embodiment of the present invention, the first insulating film 14 may be formed by depositing a high-density insulating material, and the second insulating film 15 may be formed by depositing a low-density insulating material. For example, the first insulating film 14 may be formed by depositing and patterning a high-density plasma (HDP) oxide. The first insulating film 14 may be formed to extend along the inner surface of the trench 13. For example, the first insulating film 14 may have a U-shaped or pipe-shaped shape that opens upward.
[0312] Since the first insulating film 14 has a high density, voids are unlikely to occur in the first insulating film 14, and therefore cracks due to voids in a subsequent heat treatment process may be eliminated or significantly reduced. The second insulating film 15 may be formed by depositing a tetraethylorthosilicate (TEOS) oxide film to a thickness sufficient to cover the polishing stop film 12 while filling the trench 13 in which the first insulating film 14 is formed. The second insulating film 15 may be formed at a deposition rate faster than that of the first insulating film 14. Since the deposition rate of the second insulating film 15 is fast, the trench 13 may be filled with the second insulating film 15 relatively quickly.
[0313] According to another embodiment of the present application, although not shown, the second insulating film 15 may be partially removed to leave the second insulating film 15 on the trench 13. For example, the second insulating film 15 may be selectively removed to define or open a specific region, such as a cell memory region of a semiconductor device, through a photo process and an etching process. As a result, a part or the whole of the second insulating film 15 on the polishing stop film 12 may be removed, and the second insulating film 15 may remain on the trench 13. The process of opening the specific region may be performed selectively, but is not necessarily required.
[0314] 5, a planarization process may be performed on the second insulating film 15. For example, the second insulating film 15 may be planarized using a chemical mechanical polishing (CMP) process. The chemical mechanical polishing process may be continued until the nitride film (polishing stop film) 12 is exposed. The chemical mechanical polishing process may be performed after the second insulating film 15 of FIG. 4 is formed. In this case, the surface on the nitride film (polishing stop film) 12 is relatively flat, or even if it is not flat, the non-flatness is not large, so that the chemical mechanical polishing process can be easily performed.
[0315] Then, referring to FIG. 6, the nitride film may be removed to form the STI. The purpose of the nitride film is to protect the upper film 11 so that the upper film 11 is not affected by the first insulating film 14. The upper film 11 is a gate oxide film that is thin and requires reliability, so it must be handled with care. When the nitride film is removed by an etching method (wet method), the wafer may be immersed in a chemical solution to etch only the nitride film without etching the oxide film. For this purpose, a solution having a high selectivity (etching ratio) to the nitride film may be used. In another embodiment of the present application, the nitride film may also be removed by CMP. In this case, the nitride film does not need to be etched, but since there is a possibility of physical damage to the oxide film, it is preferable to protect the oxide film by chemically treating the nitride film by etching.
[0316] According to another embodiment of the present application, the chemical mechanical polishing (CMP) process completely removes the first insulating film 14 and the second insulating film 15 on the nitride film (polishing stop film, 12) after gap filling, thereby isolating the active region and the field region, and can be roughly divided into three steps as shown in FIG. 7.
[0317] In the first step, local planarization is performed by performing bulk CMP of the second insulating film 15 on a platen. In the second step, the second insulating film 15, whose step has been reduced, is cleaned or polished on a platen, and polishing is stopped when the nitride film (polishing stop film) 12 is exposed. At this time, a polishing end point detection (EPD) is used to detect the time when the different film material is exposed. In the third step, residues of the second insulating film 15 that may remain on the nitride film (polishing stop film) 12 are removed on a platen, and the nitride film and oxide film materials may be polished to perform targeting.
[0318] 8 shows the structure of a chemical mechanical polishing (CMP) equipment according to an embodiment of the present application. This equipment is characterized in that it is composed of three platens, and as described above, the STI CMP polishing may proceed stepwise through platens 1, 2, and 3. After polishing, the wafer is moved to a cleaning section, where cleaning is completed to end the process.
[0319] In addition, in the method for manufacturing a semiconductor device according to an embodiment of the present application, the method for simultaneously polishing a silicon oxide film, a silicon nitride film, and a polysilicon film using the chemical mechanical polishing slurry composition is not limited, and any conventional commonly used polishing method and conditions may be used, and the present invention is not particularly limited thereto.
[0320] The slurry composition for chemical mechanical polishing according to an embodiment of the present disclosure has high dispersion stability and high Ce on the surface of the cerium oxide particles contained in the slurry composition. 3+ Because of its high ceria content, it can increase the polishing rate of silicon-containing substrates through a chemical polishing mechanism that forms Si-O-Ce between silica and cerium, and even under conditions where the ceria content is low, it can be effectively used to remove silicon oxide films, in particular, from the surface of semiconductor devices in the CMP process.
[0321] A fourth aspect of the present invention provides a semiconductor device comprising: a substrate; and a trench filled with an insulating material on the substrate; the trench is produced by polishing at least one film selected from the group consisting of a silicon oxide film, a silicon nitride film, and a polysilicon film, using a slurry composition for chemical mechanical polishing, the slurry composition for chemical mechanical polishing comprising cerium oxide particles and a solvent, and an aqueous dispersion in which the content of the cerium oxide particles is adjusted to 1.0 wt % has an optical transmittance of 5550% or more for light with a wavelength of 500 nm.
[0322] Detailed explanations of parts that overlap with the first to third aspects of the present application will be omitted, but the contents explained for the first to third aspects of the present application may be similarly applied to the fourth aspect even if the explanation is omitted.
[0323] A fifth aspect of the present invention provides a method for producing cerium oxide particles for chemical mechanical polishing, comprising the steps of: preparing a raw material precursor; and grinding or precipitating cerium oxide particles in a solution containing the raw material precursor to obtain a dispersion of cerium oxide particles for chemical mechanical polishing, wherein the aqueous dispersion in which the cerium oxide particle content is adjusted to 1.0 wt % has a light transmittance of 50% or more for light with a wavelength of 500 nm.
[0324] Detailed descriptions of parts that overlap with the first to fourth aspects of the present application will be omitted, but the contents described for the first to fourth aspects of the present application may be similarly applied to the fifth aspect even if the description is omitted.
[0325] In an embodiment of the present disclosure, the method may further include preparing a raw material precursor. The raw material precursor may be any precursor material capable of producing cerium oxide particles as a product.
[0326] In one embodiment of the present application, the method may include a step of obtaining a dispersion of cerium oxide particles for chemical mechanical polishing by grinding or precipitating cerium oxide particles in a solution containing a raw material precursor. The step of grinding cerium oxide particles in a solution containing a raw material precursor may be, for example, grinding by a milling process, and the grinding method may be determined within the scope of the technical common sense of a person skilled in the art and is not limited. In the case of the step of obtaining a dispersion of cerium oxide particles by precipitating cerium oxide particles in a solution containing a raw material precursor, the method may further include a step of removing a supernatant liquid or a step of filtering.
[0327] In an embodiment of the present application, the cerium precursor may be at least one selected from the group consisting of cerium ammonium nitrate, cerium nitrate, cerium ammonium sulfate, cerium acetate, cerium chloride, cerium hydroxide, and cerium oxide.
[0328] In an embodiment of the present application, the filtering step may be performed using a non-limiting filtering device, more preferably a filtering device having a membrane. In the case of the cerium oxide particles produced by the method according to an embodiment of the present application, it can be understood that not only is the synthesis of the cerium oxide particles itself performed in high yield, but most of the cerium precursor material is removed by an additional filtering step.
[0329] The above description of the present invention is for illustrative purposes only, and a person having ordinary skill in the art to which the present invention pertains will understand that the present invention can be easily modified into other specific forms without changing the technical concept or essential configuration of the present invention. Therefore, it should be understood that the above-described embodiments are illustrative in all respects and are not limiting. For example, each component described as a single type can be implemented in a distributed form, and similarly, each component described as a distributed type can be implemented in a combined form.
[0330] The scope of the present invention is defined by the claims set forth below, and all modifications and variations that fall within the meaning and scope of the claims and their equivalent concepts should be construed as being included within the scope of the present invention. [Industrial Applicability]
[0331] In the case of the cerium oxide particles according to one embodiment of the present invention, the Ce on the surface of the cerium oxide 3+ By increasing the ratio of , when contained in a slurry for chemical mechanical polishing, a high oxide film removal rate can be maintained even at a low content, despite the small particle size.
[0332] In addition, according to one embodiment of the present invention, it is possible to provide cerium oxide particles for a slurry composition for chemical mechanical polishing, which can minimize surface defects on a wafer and maximize the oxide film removal rate, unlike the correlation between surface defects and oxide film removal rate that has been conventionally considered to be in a trade-off relationship, and can minimize surface defects while maximizing the oxide film removal rate.
[0333] In addition, according to one embodiment of the present invention, it is confirmed that the addition of a cationic polymer further increases the oxide film polishing rate and at the same time increases the oxide film / polysilicon film selectivity. Considering the conventional technical common sense that the addition of a cationic polymer usually sacrifices the polishing rate to secure other properties, this can be said to be a unique effect of the present invention.
[0334] The effects of the present invention are not limited to the effects described above, but should be understood to include all effects that can be inferred from the configuration of the invention described in the detailed description of the present invention or the claims.
Claims
1. Cerium oxide particles for chemical mechanical polishing, comprising: The electron energy loss spectroscopy (EELS) spectrum for the cerium oxide particles includes a first peak at 876.5 to 886.5 eV and a second peak at 894.5 to 904.5 eV; the maximum intensity of the first peak is greater than the maximum intensity of the second peak; Further comprising a third peak at 886.5 to 889.5 eV and a fourth peak at 904.5 to 908.5 eV; a ratio ((P 1 +P 2 ) / P t ) of the sum of the areas of the third peak section (P 1 ) and the sum of the areas of the fourth peak section (P 2 ) to the sum of all areas of the peaks of the spectrum (P t ) is 0.1 or less; In an aqueous dispersion in which the content of the cerium oxide particles is adjusted to 1.0% by weight, the light transmittance for light with a wavelength of 500 nm is 50% or more, When the particle size of the cerium oxide particles measured by a dynamic light scattering (DLS) particle size analyzer is a and the particle size of the cerium oxide particles measured by a transmission electron microscope (TEM) is b, the following formula can be obtained: [0010] 1. The cerium oxide particles for chemical mechanical polishing,
2. 2. The cerium oxide particles for chemical mechanical polishing according to claim 1, characterized in that in an aqueous dispersion in which the content of the cerium oxide particles is adjusted to 1.0 wt %, the average light transmittance for light having a wavelength of 450 to 800 nm is 50% or more.
3. 2. The cerium oxide particles for chemical mechanical polishing according to claim 1, wherein the secondary particle diameter of the cerium oxide particles is 1 to 30 nm as measured by a dynamic light scattering (DLS) particle size analyzer.
4. 2. The cerium oxide particles for chemical mechanical polishing according to claim 1, wherein the secondary particle diameter of the cerium oxide particles is 1 to 20 nm as measured by a dynamic light scattering (DLS) particle size analyzer.
5. 2. The cerium oxide particles for chemical mechanical polishing according to claim 1, wherein the primary particle diameter of the cerium oxide particles is 0.5 to 11 nm when analyzed by X-ray diffraction (XRD).
6. Cerium oxide particles for chemical mechanical polishing, comprising: When the surface of the cerium oxide particles is analyzed by X-ray photoelectron spectroscopy (XPS), XPS peaks showing Ce—O bond energy indicative of Ce 3+ appear at a first peak of 900.2 to 902.2 eV, a second peak of 896.4 to 898.4 eV, a third peak of 885.3 to 887.3 eV, and a fourth peak of 880.1 to 882.1 eV; In the X-ray photoelectron spectroscopy (XPS) analysis, the ratio of Ce to the sum of the XPS peak areas showing the Ce-O bond energy on the surface of the cerium oxide particles is 3+ The ratio of the sum of the XPS peak areas for the Ce—O bond energies is 0.29 to 0.70, In an aqueous dispersion in which the content of the cerium oxide particles is adjusted to 1.0% by weight, the light transmittance for light with a wavelength of 500 nm is 50% or more, When the particle size of the cerium oxide particles measured by a dynamic light scattering (DLS) particle size analyzer is a and the particle size of the cerium oxide particles measured by a transmission electron microscope (TEM) is b, the following formula can be obtained: [0025] 1. The cerium oxide particles for chemical mechanical polishing, 7. The cerium oxide particles according to claim 1 or claim 6; and A solvent; A slurry composition for chemical mechanical polishing.
8. 8. The chemical mechanical polishing slurry composition of claim 7, wherein the cerium oxide particles are included in an amount of 0.01 to 5 parts by weight based on 100 parts by weight of the total slurry composition.
9. 8. The chemical mechanical polishing slurry composition according to claim 7, wherein the pH of the composition is 2-10.
10. 8. The slurry composition for chemical mechanical polishing according to claim 7, characterized in that it comprises one or more inorganic acids selected from the group consisting of sulfuric acid, hydrochloric acid, nitric acid, and phosphoric acid; one or more organic acids selected from the group consisting of acetic acid, citric acid, glutaric acid, glycolic acid, formic acid, lactic acid, malic acid, malonic acid, maleic acid, oxalic acid, phthalic acid, succinic acid, and tartaric acid; one or more amino acids selected from the group consisting of lysine, glycine, alanine, arginine, valine, leucine, isoleucine, methionine, cysteine, proline, histidine, phenylalanine, serine, tricine, tyrosine, aspartic acid, tryptophan, and aminobutyric acid; imidazole; alkylamines; alcoholamines; quaternary amine hydroxides; ammonia; or combinations thereof.
11. 8. The chemical mechanical polishing slurry composition of claim 7, wherein the solvent is deionized water.
12. 8. The chemical mechanical polishing slurry composition according to claim 7, wherein the chemical mechanical polishing slurry composition has a polishing rate for a silicon oxide film of 1,000 to 5,000 Å / min.
13. A method for manufacturing a semiconductor device, comprising a step of polishing with the chemical mechanical polishing slurry composition according to claim 7.
14. Providing a feed precursor; and pulverizing or precipitating cerium oxide particles in a solution containing the raw material precursor to obtain a dispersion of cerium oxide particles for chemical mechanical polishing; A method for producing cerium oxide particles for chemical mechanical polishing as described in claim 1 or claim 6, characterized in that in an aqueous dispersion in which the content of the cerium oxide particles is adjusted to 1.0 weight %, the light transmittance for light with a wavelength of 500 nm is 50% or more.
Citation Information
Patent Citations
Abrasive composition for chemical mechanical polishing and method of use thereof
JP2012503880A
Polishing particles for polishing silicon oxide film
JP2016127139A
Polishing liquid composition for silicon oxide film
JP2020080399A
Slurry comprising for sti polishing
KR1020170004462A
Rare-earth permanent magnet
WO2015159612A1